Particle dispersed liquid and production method thereof
The use of a dispersion of hollow silica particles with specific properties as a resist material in photolithography addresses the challenges of achieving a low refractive index and minimizing pattern roughness and residue formation, resulting in high development properties and resolution.
Patent Information
- Application Number
- JP2023158297
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
AI Technical Summary
Existing resist films used in photolithography face challenges in achieving a low refractive index while minimizing pattern roughness and residue formation, due to issues with particle desorption and compatibility with alkaline developers.
A dispersion of hollow silica particles with a silicon-containing outer shell, a cavity inside, and a specific range of average particle size, refractive index, and silanol group density, along with a high proportion of particles with aspect ratios between 1.50 and 5.00, is used as a resist material. This dispersion is produced through a method involving aqueous alkaline solutions, acid treatment, and heat processing.
The use of this particle dispersion in resist films results in high development properties, reduced pattern roughness, and minimal residue formation, while achieving a low refractive index and high resolution.
Smart Images

Figure 2025049841000011 
Figure 2025049841000012 
Figure 2025049841000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a dispersion of hollow silica particles and a method for producing the same. [Background technology]
[0002] In recent years, photolithography, which is used in the manufacture of semiconductor elements, printed circuit boards, liquid crystal display panels, organic EL display panels, etc., is a technique that has become widespread in which a photosensitive substance is applied to a substrate, and then exposed and developed in a pattern to process the substrate. The photosensitive material (resist material) used in this photolithography is a material that forms a functional film, such as a low refractive index film (or a high refractive index film) or an insulating film, in a pattern on the substrate surface. For this reason, high sensitivity, high resolution, and high transparency are required. Such functional films are formed by patterning into a desired shape using a resist material. This resist material is composed of components such as a resin component, a polymerization initiator, and a solvent.
[0003] It has been known that hollow silica particles or low-refractive-index particles with a porous interior are used in coating solutions as a means of lowering the refractive index of a film. For example, JP 2019-119848 A (Patent Document 1) and JP 2020-166156 A (Patent Document 2) disclose the use of silica particles containing gas in the particles as a photosensitive resin composition to lower the refractive index of the film. In addition, WO 2010 / 071010 (Patent Document 3) describes chain-like silica-based hollow fine particles in which silica-based hollow fine particles are linked in a chain shape. Furthermore, JP 2009-020520 A (Patent Document 4) describes a photosensitive resin composition with excellent low dielectric properties, adhesive strength, heat resistance, etc., and discloses the use of colloidal inorganic nanoparticles surface-treated with an organic silane. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-119848 A [Patent Document 2] JP 2020-166156 A [Patent Document 3] International Publication No. 2010 / 071010 [Patent Document 4] JP 2009-020520 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the electronics field, components such as circuit boards and elements are produced using resist films. In such a multi-layer structure of resist films, a pattern film with a low refractive index is required to impart a microlens function and an anti-reflection function. Examples of such low refractive index particles include "particles having a cavity inside the outer shell," so-called "hollow particles." However, when a resist film containing such particles is developed to form a pattern, the particles are likely to detach from the pattern portion, causing particle-derived residues on the substrate, and there is a concern that a sharp pattern cannot be obtained (so-called pattern roughness). Thus, the residues and pattern roughness in the resist film formation process have a significant impact on the quality of the device.
[0006] In addition, when hollow particles with a "high porosity", i.e., hollow particles with a "large particle size", are blended as low refractive index particles, the surface unevenness of the pattern portion increases, and pattern roughness is likely to occur. On the other hand, when hollow particles with a "small particle size" are blended to suppress the surface unevenness of the pattern portion, the hollow particles have a low porosity and a high refractive index compared to hollow particles with a large particle size, so the reduction in the refractive index of the film is insufficient. Furthermore, even if the blending amount of hollow particles is increased to lower the refractive index of the film, the surface unevenness increases due to the small amount of resin component that can exist between the particles, and pattern roughness is likely to occur. In other words, the lowering of the refractive index of the resist film by blending particles needs to suppress particle detachment and to achieve both the refractive index and the flattening of the surface unevenness.
[0007] When the particles described in Patent Document 1 and Patent Document 2 are used in a resist material, it is expected to obtain a film with a low refractive index, but since the number density of the silanol groups on the particle surface is low, the compatibility with an alkaline developer is low, and there are problems of pattern roughness and particle detachment from the pattern part, and particle-derived residues are generated on the substrate. In addition, when the particles described in Patent Document 3 are used in a resist material, it is expected to obtain a film with a low refractive index, but since the number density of the silanol groups on the particle surface is high, the dispersibility in the resist film is low, and it is difficult to form a pattern. Furthermore, since the particles described in Patent Document 4 are surface-treated with an organic silane, although the dispersibility in the resist film is high, the compatibility with an alkaline developer is low, and there are problems of pattern roughness and particle-derived residues on the substrate.
[0008] If residues derived from particles are present, there is a risk of open / short defects due to destruction of the wiring pattern and a decrease in operating speed. Factors causing residues in resist films containing particles include, for example, insufficient compatibility with alkaline developers, insufficient rinsing after development, particle detachment from the patterned portion, and dissolution of the patterned film by a solvent during formation of the upper resist film. Among these, residues due to particle detachment from the patterned portion and dissolution of the patterned film during formation of the upper resist film occur in the process after the development process. This may lead to insufficient formation of the multilayer structure of the resist film and at the same time to collapse of the pattern. For this reason, it is required that the particles are not easily detached from the patterned portion even during formation of the upper resist film. Here, it is assumed that the dissolution of the patterned film during formation of the upper resist film is caused by the penetration of the solvent of the resist liquid applied to the upper layer into the interface between the particles and the resin in the patterned film. If the amount of hollow particles is reduced in order to suppress particle detachment from the patterned portion, it may be difficult to obtain a film with a low refractive index. Moreover, if the bonding between the particles and the resin is strengthened, the bonding with the resin becomes excessive, which may make development difficult. In addition, the compatibility with an alkaline developer decreases, which may make it easier for particle-derived residues to be generated on the substrate. [Means for solving the problem]
[0009] To solve these problems, we discovered a dispersion of particles as follows. These particles have an outer shell containing silicon and a cavity inside. These particles have an average particle size of 15 to 150 nm, a refractive index of 1.08 to 1.35, and a number density of silanol groups on the particle surface calculated by the Sears measurement method of 0.5 to 2.5 / nm. 2 Among these particles, the proportion of particles having an aspect ratio of 1.50 to 5.00 is 50% or more.
[0010] Hereinafter, these particles may be simply referred to as "particles" or "particles in a dispersion liquid".
[0011] These particles have a low refractive index and a high ratio of particles with a high aspect ratio. When these particles are used in a resist material, a film with little particle detachment from the pattern, i.e., little residue or pattern roughness, can be obtained, and a film with similar properties can be obtained even after forming an upper resist film. Therefore, it exhibits excellent developability as a multi-layered resist film.
[0012] In order to obtain these particles, the following production method was found.
[0013] First, an alkaline aqueous solution is prepared (first step). A solution of a compound containing silicon and an aqueous solution of an alkali-soluble compound of an inorganic element other than silicon are mixed with this, and an oxide of silicon (SiO 2 When oxides of inorganic elements other than silicon are expressed as MOx, the concentrations of a solution of a compound containing silicon and an aqueous solution of an alkali-soluble compound of an inorganic element other than silicon are, respectively, SiO 2 Then, the mixture is added simultaneously to the aqueous alkali solution so that the MOx content is 3.1 to 10.0 mass % and the solid content of the dispersion is 2.5 mass % or more for a certain period of time to prepare a dispersion of composite oxide particles a (second step). 2), a solution of a compound containing silicon and an aqueous solution of an alkali-soluble compound of an inorganic element other than silicon are added to prepare a dispersion of composite oxide particles b (third step). Next, an acid is added to the dispersion of composite oxide particles b to remove at least a part of the elements other than silicon constituting composite oxide particles b, thereby preparing a dispersion of silica-based particles (fourth step). The dispersion of silica-based particles obtained in the fourth step is heated to 60 to 200°C, and then cooled to less than 50°C (fifth step).
[0014] The properties of the particles in the dispersion obtained by this production method are similar to those of the particles in the dispersion described above. Effect of the Invention
[0015] When the dispersion of the particles of the present invention is used in a resist material, a film having high developability and little residue and pattern roughness can be obtained, and a pattern film having similar properties can be realized even after forming a multi-layered resist film. The resist film obtained here has a low refractive index, low haze, and high resolution. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic diagram of a cross section of a particle according to the present invention. [Diagram 2] FIG. 2 is a diagram for explaining the definition of the major axis and minor axis of the cavity of a particle in which the cavities are connected to each other. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] [Particle dispersion] The particle dispersion according to the present invention (hereinafter, this may be simply referred to as "dispersion") will be described.
[0018] The dispersion of the present invention contains particles having a silicon-containing shell with a cavity inside, and a dispersion medium. The particles have an average particle size of 15 to 150 nm, a refractive index of 1.08 to 1.35, and a number density of silanol groups on the particle surface calculated by the Sears measurement method of 0.5 to 2.5 / nm. 2Among these, the proportion of particles having an aspect ratio of 1.50 to 5.00 is 50% or more.
[0019] A schematic diagram of a cross section of a particle according to the present invention is shown in FIG.
[0020] The particles have an average particle diameter of 15 to 150 nm, which is determined by taking a photograph at a specified magnification using a transmission electron microscope (TEM), randomly selecting 300 particles from the photograph (TEM photograph), processing the image to determine the particle area, and calculating the average value of the equivalent circle diameter from the area.
[0021] Here, particles with an average particle diameter of less than 15 nm have a small ratio of voids (porosity) in the particles, and the refractive index is not sufficiently low, so the refractive index of the resist film may not be sufficiently low. Conversely, if the particle diameter exceeds 150 nm, depending on the content, pattern roughness may occur. The average particle diameter is preferably 20 to 100 nm, more preferably 20 to 75 nm, even more preferably 20 to 55 nm, and particularly preferably 25 to 45 nm.
[0022] The refractive index of the particles is 1.08 to 1.35. When the refractive index is within this range, a resist film with a low refractive index can be obtained by using the particles in a resist material. Here, it is difficult to obtain particles with a refractive index of less than 1.08. On the other hand, when the refractive index exceeds 1.35, the refractive index of the resist film may not be sufficiently reduced. The refractive index is preferably 1.08 to 1.30, more preferably 1.08 to 1.25.
[0023] The number density of silanol groups on the particle surface calculated by the Sears measurement method is 0.5 to 2.5 / nm 2 When the silanol group density is within this range, compatibility with an alkaline developer is high, and therefore a resist film with excellent developability can be obtained.
[0024] Here, the number density of silanol groups is 0.5 / nm 2If the density is less than 2.5 particles / nm, the compatibility with the alkaline developer is low, which may cause pattern roughness or particle-derived residues to be left on the substrate. 2 If the density of silanol groups exceeds 100%, the bond with the resin becomes insufficient. Therefore, the bond with the resin is weak, and it may be difficult to form a pattern. The silanol group density is preferably 0.8 to 2.2 groups / nm 2 , more preferably 1.0 to 2.0 particles / nm 2 It is.
[0025] The number density of silanol groups of particles is calculated from the Sears number and the specific surface area. The Sears number is measured by titration with sodium hydroxide (NaOH) according to the description by Sears in Analytical Chemistry 28 (1956), 12, 1981-1983. Specifically, 30 g of sodium chloride is added to 150 g of silica particles diluted with pure water to make the silica particle concentration 1% by mass, and the pH is adjusted to 4.0 with hydrochloric acid. Then, 0.1 N NaOH aqueous solution is titrated at 0.1 ml / sec., and the number density is expressed by the amount (Q) of NaOH aqueous solution required to reach pH 9.0. That is, the Sears number (A) is the amount of 0.1 N NaOH aqueous solution required to titrate 1.5 g of particles, and is expressed by the following formula (1).
[0026] A=(Q×f×100×1.5) / (W×C) ···(1) (In the formula, f represents the titer of the 0.1N NaOH aqueous solution used, C represents the particle concentration (mass%) in the dispersion, and W represents the amount (g) of the dispersion collected.)
[0027] The number density (ρ) of silanol groups is expressed by the following formula (2).
[0028] ρ = (B × N A ) / (10 18 ×M×S BET ) ···(2) (In the formula, B is the amount of NaOH (mol) required to change the pH from 4.0 to 9.0 per 1.5 g of particles calculated from the Sears number (A), N Ais the Avogadro number (particles / mol), M is the particle mass (1.5g), and S BET is the specific surface area (m2) measured by the BET method using nitrogen adsorption. 2 / g).
[0029] The proportion of particles with an aspect ratio of 1.50 to 5.00 among the particles is 50% or more. This is determined by taking a photograph at a specified magnification using a transmission electron microscope (TEM), measuring the major and minor axes of 300 randomly selected particles in the photograph (TEM photograph), calculating the aspect ratio, which is the ratio of the major and minor axes, counting the particles with an aspect ratio of 1.50 to 5.00, and determining the proportion of that number to the total number of particles.
[0030] When the aspect ratio of the particles is within this range, by using the particles in the resist material, a multi-layered resist film with less residue and less pattern roughness can be obtained even after the formation of the upper resist film. Here, particles with an aspect ratio of less than 1.50 are likely to cause particle detachment from the patterned portion because the solvent of the resist solution forming the upper resist film easily penetrates into the interface between the particles and the resin in the patterned film, and there is a risk of generating residue. In particular, when the ratio of particles in the resist film is increased for the purpose of lowering the refractive index of the resist film, particle detachment is likely to occur as the ratio of the matrix component becomes relatively lower. By using particles with a high aspect ratio, in addition to being able to reduce the interface between the particles and the resin in the patterned film through which the solvent penetrates, the anchoring effect of the particles on the resin works, and particle detachment is suppressed. However, when particles with an aspect ratio of more than 5.00 are used, there is a risk of pattern roughness occurring, depending on the content. This aspect ratio is preferably 1.50 to 4.25, more preferably 1.75 to 3.50.
[0031] In addition, when the number ratio of particles having an aspect ratio of 1.50 to 5.00 is 50% or more, by using these particles in a resist material, particle detachment from the pattern portion is suppressed, and a multi-layered resist film with less residue and pattern roughness can be obtained even after forming an upper resist film. Here, when the number ratio is less than 50%, particle detachment from the pattern portion is likely to occur, and residue and pattern roughness may occur. This number ratio is preferably 60% or more, more preferably 70% or more, even more preferably 80% or more, particularly preferably 90% or more, and most preferably 100%.
[0032] The average aspect ratio of the particles is preferably 1.25 to 5.00, which is obtained by taking a photograph at a specified magnification using a transmission electron microscope (TEM), measuring the major axis and minor axis of any 300 particles in the photograph (TEM photograph), calculating the ratio of the major axis to the minor axis, and averaging the ratio.
[0033] When the average aspect ratio of particles that account for 50% or more is within this range, a multi-layered resist film with less residue and less pattern roughness can be obtained by using this particle in a resist material. Here, particles with an average aspect ratio of less than 1.25 are likely to cause particle detachment from the patterned portion because the solvent of the resist solution that forms the upper resist film is likely to penetrate into the interface between the particles and the resin in the patterned film, which may result in the generation of residue. In particular, when the ratio of particles in the resist film is increased in order to reduce the refractive index of the resist film, the relatively lower ratio of the matrix component makes it more likely that particle detachment will occur. By using particles with a high aspect ratio, the interface between the particles and the resin in the patterned film through which the solvent penetrates can be reduced, and the anchoring effect of the particles on the resin works, suppressing the detachment of the particles. However, when particles with an average aspect ratio of more than 5.00 are used, pattern roughness may occur, depending on the content. By the way, this average aspect ratio is calculated by calculating the aspect ratio of each particle and calculating the average value. Therefore, for example, if the average of the particle group with the aspect ratio less than the lower limit of 1.50 to 5.00 and the particle group with the aspect ratio exceeding the upper limit is taken, this average aspect ratio range may be obtained. However, as described above, when particles with aspect ratios outside the range of 1.50 to 5.00 are used in a resist material, they are not preferable as a resist film, so it is preferable that the majority of the particles satisfying this average aspect ratio range are composed of particles with aspect ratios of 1.50 to 5.00. This average aspect ratio is preferably 1.50 to 4.50, more preferably 1.75 to 4.00.
[0034] The shape of the particles is not particularly limited. Examples include peanut-shaped, chain-shaped, ellipsoidal, confetti-shaped, spherical, etc. Among them, peanut-shaped and chain-shaped particles are preferred because they are less likely to detach from the pattern portion and suppress the occurrence of residues and pattern roughness even after the formation of the upper resist film.
[0035] The thickness of the shell of the particle is preferably 3 to 12 nm, which is the average value of the following: for 300 random particles in a TEM photograph, image processing is performed to determine the area of the cavity of the particle, the circle equivalent diameter is calculated from the area, this is subtracted from each particle diameter, and the result is divided by 2.
[0036] If the thickness of the shell is less than 3 nm, it may be difficult to obtain the strength required to maintain the particle shape. On the other hand, if the thickness exceeds 12 nm, it may be difficult to obtain a resist film with a low refractive index due to the high particle refractive index. The thickness of the shell is more preferably 3 to 9 nm, even more preferably 3 to 7 nm, and particularly preferably 3 to 5 nm.
[0037] The ratio of the shell thickness to the particle diameter of the particles is preferably 3 to 30%. When this ratio is within this range, a resist film with a low refractive index can be obtained.
[0038] Here, if the ratio is less than 3%, it may be difficult to obtain the strength required to maintain the particle shape, and therefore it may be difficult to obtain the particles themselves. Conversely, if the ratio exceeds 30%, the refractive index may not be sufficiently low, and therefore it may be difficult to obtain the desired resist film. This ratio is more preferably 5 to 25%, and even more preferably 7 to 20%.
[0039] The average aspect ratio of the cavity of the particle is preferably 1.00 to 6.50. This is obtained by taking a photograph at a predetermined magnification using a transmission electron microscope (TEM), measuring the major axis and minor axis of the cavity inside the outer shell of any 300 particles in the photograph (TEM photograph), calculating the ratio of the major axis to the minor axis, and calculating the average value. This cavity may exist alone or in a plurality of forms in the particle. In some of these, a shape in which the cavities are connected may be observed. For such particles in which the cavities are connected, the major axis and minor axis of the cavities are defined as shown in FIG. 2. The average aspect ratio of the cavity of the particle is more preferably 1.25 to 5.00, and even more preferably 1.50 to 3.50.
[0040] The cavity inside the shell of the particle is preferably shaped to follow the particle's outer shape. This is because, although it depends on the thickness of the shell, the shell has a uniform thickness, which makes it easier to obtain the strength required to maintain the particle's shape when stress is applied to the particle. Furthermore, it is preferable that the cavity has a shape similar to the particle's shape. This is because the increased porosity of the particle makes it easier to obtain a resist film with a low refractive index.
[0041] In order to reduce the refractive index and obtain a transparent film, it is preferable that the cavity is substantially one cavity. Here, "substantially one cavity" means that the "ratio of particles having one cavity inside the shell" is 90% or more, although some particles may have "particles having multiple cavities inside the shell" due to particle coalescence or the like. The "number ratio of particles having one cavity inside the shell" is more preferably 95% or more, even more preferably 98% or more, particularly preferably 99% or more, and most preferably 100%.
[0042] The porosity of the particles is preferably 10 to 85%. When the porosity is in this range, a resist film with a low refractive index can be obtained.
[0043] Here, if the porosity is less than 10%, the refractive index is not sufficiently low, so it may be difficult to obtain a desired resist film. Conversely, if the porosity is more than 85%, it may be difficult to obtain the strength required to maintain the particle shape, so it may be difficult to obtain the particle itself. The porosity is more preferably 20 to 85%, and even more preferably 30 to 85%.
[0044] Based on appearance, particles can be broadly classified into unconnected particles, which are observed singly, such as the above-mentioned ellipsoidal, confetti-like, and spherical particles, and connected particles, which have ``necks'' that appear to be made up of multiple particles joined together, such as peanut-like and chain-like particles.
[0045] The weighted average of the minor diameters of the non-linked particles and the "diameter of the constricted portion" of the linked particles as shown in Figure 1 is defined as Dn. The average of the minor diameters of the non-linked particles and the minor diameters of the individual linked particles is defined as the average primary particle diameter (Df). Here, the minor diameter of the non-linked particles means the largest diameter perpendicular to the major diameter of the particle.
[0046] The ratio (Dn / Df) of the weighted average (Dn) of the minor axis of the non-linked particles and the "diameter of the constricted portion" of the linked particles to the average primary particle diameter (Df) is preferably 0.20 to 0.95. This is the ratio between the average (Dn) calculated by measuring the minor axis of the non-linked particles and the "diameter of the constricted portion" of the linked particles for 300 random particles taken at a predetermined magnification using a transmission electron microscope (TEM) and the minor axis of each linked particle of the linked particles and calculating the average value as the average primary particle diameter (Df).
[0047] When the ratio (Dn / Df) is within this range, a multi-layered resist film with little residue and pattern roughness can be obtained even after the formation of the upper resist film. Here, when the ratio (Dn / Df) is less than 0.20, the bonding strength between the particles is low, so that particle defects (cracks and chips) are likely to occur at the bonding parts, and there is a risk of residue and pattern roughness. Conversely, when it exceeds 0.95, there are few interfaces between the particles and the resin in the pattern film, and the anchoring effect with the resin is difficult to work, so that particles are likely to detach from the pattern part during the formation of the upper resist film, and there is a risk of residue and pattern roughness. This ratio (Dn / Df) is preferably 0.30 to 0.85, more preferably 0.40 to 0.80.
[0048] The ratio (A1 / A2) of the specific surface area (A1) determined by pulse NMR measurement of the aqueous dispersion of the particles to the specific surface area (A2) of the particles determined from the average particle diameter (D) by image analysis of the particles is preferably 0.60 or more. The upper limit of the ratio (A1 / A2) is 1.00. The ratio (A1 / A2) being in this range indicates high compatibility with an alkaline developer. When such particles are used in a resist material, a resist film with excellent developability can be obtained.
[0049] Here, if the ratio (A1 / A2) is less than 0.60, pattern roughness may occur. This ratio (A1 / A2) is more preferably 0.65 or more, and further preferably 0.70 or more.
[0050] Pulsed NMR is a measurement method in which magnetization in a thermal equilibrium state in a static magnetic field is excited by irradiating it with pulsed radio waves of several tens of MHz, and the phenomenon in which the excited magnetization returns to the original thermal equilibrium state over time is observed. Liquid molecules in contact with or adsorbed onto the particle surface respond differently to changes in the magnetic field than liquid molecules in a free state that are not in contact with the particle surface.
[0051] In general, the motion of liquid molecules adsorbed to particle surfaces is restricted, while liquid molecules not adsorbed to particle surfaces can move freely. As a result, the relaxation time of liquid molecules adsorbed to particle surfaces is shorter than the relaxation time of other liquid molecules. The relaxation time observed in a liquid containing dispersed particles is the average of two relaxation times reflecting the liquid volume concentration on the particle surfaces and the liquid volume concentration in the free state.
[0052] Incidentally, the specific surface area (A1) of particles in a dispersion liquid determined by pulse NMR measurement indicates the specific surface area of the part of the particle that is wetted by the dispersion medium. Particles that have been surface-treated with an organosilicon compound have fewer silanol groups on the particle surface than the original particles due to the reaction between the organosilicon compound and the silanol groups on the particle surface, so the specific surface area of the part of the particle that is wetted by the hydrophilic dispersion medium is smaller. For this reason, the value of this specific surface area (A1) changes depending on the degree of surface treatment of the particles with an organosilicon compound. The value of the specific surface area (A1) also changes depending on the type of dispersion medium used during measurement.
[0053] Therefore, the ratio (A1 / A2) is an index as to the amount of the organosilicon compound contained in the surface-treated particles.
[0054] The specific surface area (A1) of the particles is obtained from the following formula (4) using the volume concentration (Ψp) of the particles calculated from the following formula (3).
[0055] Ψp=(Sc / Sd) / [(1-Sc) / Td]...Equation (3) (In the formula, Sc is the solid concentration of the particles in the dispersion (% by mass), and Sd is the density of the particles (g / cm 3 ), and Td is the density of the dispersion medium at 25°C (g / cm 3 ) is shown.
[0056] Here, the solid content concentration is the concentration of particles converted into solid content in the dispersion liquid (hereinafter the same). Sd is the sum of the value obtained by multiplying the density of the constituent components of the particle by their volume ratio and the value obtained by multiplying the density of the constituent components inside the particle by their volume ratio. Here, the following values are used for the particle components: silica: 2.2, alumina: 3.9, arsenic (III) oxide: 3.7, boron oxide: 1.9, bismuth (III) oxide: 8.9, cadmium (II) oxide: 8.2, cobalt (II) oxide: 6.1, iron (III) oxide: 5.2, gallium (III) oxide: 5.9, germanium (II) oxide: 4.2, indium oxide: 7.2, lead (II) oxide: 9.5, antimony (V) oxide: 5.2, tin oxide: 6.9, titania (anatase): 3.0, titania (rutile): 4.3, vanadium (II) oxide: 5.8, zinc oxide: 5.6, and zirconia: 6.0 (unit: g / cm). 3 ) In addition, when the particle is a composite oxide particle, a particle containing a mixture of oxides, or a mixture of oxide particles, Sd can be calculated according to the ratio of the oxides. In addition, when the constituent component inside the particle is air, Sd is 0.0 g / cm 3 , and in the case of other gases or liquids, the density corresponding thereto is used. For example, in the case of the particles of the present invention, the porosity is used as the volume ratio of the hollow parts. The porosity of a particle is defined as the ratio of the hollow parts in the particle to the total volume of the particle. Specifically, first, a TEM photograph of the particle is taken. At this time, the hollow parts of the particle have a low density, so the contrast of that part is low. Conversely, the outer shell part has a high density, so the contrast of that part is high. The hollow parts and the outer shell part of the particle can be confirmed by this contrast difference. More specifically, image processing is performed on any 300 particles in the TEM photograph to determine the area of the hollow parts, and the circle equivalent diameter is calculated from the area, which is taken as the average diameter of the hollow parts. The shape of the particles at this time is assumed to be a perfect sphere, and the average volume of the primary particles and the average volume of the hollow parts are calculated. The porosity is expressed as the ratio of the average volume of the hollow parts to the average volume of the primary particles. Furthermore, when the dispersion medium is water, for example, Td is 1.00 g / cm 3If other types of dispersion media or mixtures of dispersion media are used, use the appropriate densities.
[0057] A1={[(Ra / Rb)-1]×Rb} / (Ka×Ψp)...Equation (4) (In the formula, A1 is the specific surface area of the particle (m 2 / g), Ra is the inverse of the relaxation time of pulse NMR in the measurement of the dispersion liquid, Rb is the inverse of the relaxation time of pulse NMR in the measurement of the dispersion medium, and Ka is a coefficient depending on the dispersion medium and particles used.
[0058] The coefficient Ka is calculated assuming that the specific surface area (A2) obtained from the average particle diameter (D) of the particles is the same as the specific surface area (A3) obtained by pulse NMR measurement of a dispersion of particles that have not been surface-treated.
[0059] The specific surface area (A2) of the particles can be calculated using the average particle diameter (D) of the particles according to the following formula (5).
[0060] A2=6000 / Sd / D...Formula (5) (where Sd is the particle density (g / cm 3 ) is shown.
[0061] The specific surface area (A3) of particles that have not been surface-treated can be obtained from equation (6) using the particle volume concentration (Ψp) obtained from equation (3).
[0062] A3={[(Rc / Rd)-1]×Rd} / (Ka×Ψp)...Equation (6) (In the formula, A3 is the specific surface area of the particle (m 2 / g), Rc is the inverse of the relaxation time of pulse NMR in the measurement of the particle dispersion, Rd is the inverse of the relaxation time of pulse NMR in the measurement of the dispersion medium, and Ka is a coefficient depending on the dispersion medium and particles used.
[0063] Here, the coefficient Ka is set so that the specific surface area (A2) and the specific surface area (A3) have the same value. Therefore, from the formulas (5) and (6), Ka={[(Rc / Rd)-1]×Rd} / (Ψp×A2)...Equation (7) It can be calculated as:
[0064] The difference between the density of a particle in helium gas and that in nitrogen gas is 0.2 to 1.2 g / cm 3 When the density difference is within this range, a resist film with a low refractive index can be obtained by blending the particles.
[0065] Here, the density difference is 0.2 g / cm 3 If it is less than 1.2 g / cm, the porosity of the particles will be small, and it may be difficult to obtain a resist film with a low refractive index. 3 It is difficult to obtain particles having a density difference exceeding this value. The difference between these densities is more preferably 0.3 to 1.0 g / cm 3 , more preferably 0.4 to 1.0 g / cm 3 It is.
[0066] The silicon content in the particles is calculated by dividing silicon by silica (SiO 2 It is preferable that the content of SiO is 98 parts by mass or more. 2 If the content is 98 parts by mass or more, a film with a low refractive index is easily obtained. Such particles are preferably used for a resist film. 2 The content is more preferably 99 parts by mass or more, further preferably 99.5 parts by mass or more, and particularly preferably substantially 100 parts by mass.
[0067] Here, "substantially 100 parts by mass" means that metal elements other than silicon may be contained as impurities, but the total amount of the metal elements other than silicon is less than 0.05 parts by mass on an oxide basis. Such high-purity particles are suitable for use in resist films used in semiconductor circuits such as highly integrated logic and memory, and optical sensors.
[0068] Thus, the constituent components of the particles preferably contain silicon (Si) as a main element. Here, the constituent components of the particles may be any of the following elements (a) to (c). These elements are derived from materials that are preferably used in preparing the particles.
[0069] (a)SiO 2 (b) An oxide containing Si and at least one element selected from Al, As, B, Bi, Cd, Co, Fe, Ga, Ge, In, Pb, Sb, Sn, Ti, V, Zn, and Zr. The oxide containing these elements may be a mixture or a composite oxide. (c) A mixture of the above (a) and (b)
[0070] Incidentally, the content of elements other than Si in the particles in the above item (b) is preferably less than 2 parts by mass on an oxide basis when the total amount of metal elements constituting the particles is expressed as 100 parts by mass on an oxide basis. Here, if this content is 2 parts by mass or more, the refractive index of the particles may increase, or it may be difficult to obtain a transparent film due to coloring or the like. This content is more preferably less than 1 part by mass, even more preferably less than 0.5 parts by mass, and particularly preferably substantially 0 parts by mass. Here, substantially 0 parts by mass means that the total amount of metal elements other than silicon is less than 0.05 parts by mass on an oxide basis. Such high-purity particles are suitably used for resist films used in semiconductor circuits such as highly integrated logic and memory, and optical sensors.
[0071] In addition, in addition to the particles listed in (a) to (c) above, "particles having an outer shell and a cavity inside it" and so-called "solid particles" that do not have a cavity inside the particle may exist, so long as the refractive index of the particle does not deviate from the range of the refractive index of the particle. The ratio of these particles other than the particles of the present invention varies depending on the type and composition ratio of the elements that make up the particle. For example, silicon is SiO 2In the case of "solid particles" containing 98 parts by mass or more as a fluorine-containing compound and having a similar average particle size, the ratio of the number of solid particles to the total number of particles is preferably less than 20%. This ratio is determined, for example, by counting the number of the particles of the present invention and solid particles in a predetermined field of view of a TEM photograph. If this ratio is 20% or more, the refractive index will be higher than the desired range, and it may be difficult to obtain a desired resist film. In the case of such solid particles, the ratio is more preferably less than 10%, even more preferably less than 5%, particularly preferably less than 1%, and most preferably 0%. If particles of different element types are present, for example, mapping is performed by energy dispersive X-ray analysis (EDS) on the particles in a predetermined field of view, and the number of the particles of the present invention and the particles of different element types is counted to determine the ratio of the particles of the present invention and other particles.
[0072] Particle 29 The area Q of the peak appearing at chemical shifts between -78 and -88 ppm in Si-NMR spectroscopy 1 and the area Q of the peak appearing at chemical shifts of -88 to -98 ppm. 2 and the area Q of the peak appearing at chemical shifts -98 to -108 ppm 3 and the area Q of the peak appearing at chemical shifts of -108 to -120 ppm. 4 In (Q 4 / ΣQ)×100 is preferably less than 90%, where ΣQ=Q 1 +Q 2 +Q 3 +Q 4 It is.
[0073] This Q 1 The peaks attributable to Q are due to one (-OSi) group and three (-OH) groups bonded to a Si atom. 2 The peaks attributable to Q are due to two (-OSi) groups and two (-OH) groups bonded to a Si atom. 3 The peaks attributable to Q are due to three (-OSi) groups and one (-OH) group bonded to a Si atom. 4 The peaks assigned to are due to four (-OSi) groups bonded to a Si atom. (Q 4When the ratio of silanol groups is in this range, the amount of silanol groups is large and compatibility with an alkaline developer is high, resulting in a resist film with excellent developability.
[0074] Here, (Q 4 If the ratio of (ΣQ) is 90% or more, the number of silanol groups is small, so the compatibility with alkaline developers is low, and there is a risk of pattern roughening or particle-derived residues being left on the substrate. (Q 4 / ΣQ) is more preferably less than 85%.
[0075] As previously mentioned, the particles have a given number density of silanol groups.
[0076] In addition to the silanol group, the particle shell preferably contains at least one functional group selected from an alkyl group, an acryloyl group, a (meth)acryloyl group, a vinyl group, a mercapto group, and an epoxy group. When the particles contain these functional groups, the particles have high dispersibility in a dispersion liquid, a coating liquid for forming a resist film, and a resin, and the bond with the resin is also improved. Among them, the alkyl group, the epoxy group, the acryloyl group, and the (meth)acryloyl group are preferred because of their high bond with the resin.
[0077] Furthermore, the particle shell preferably contains at least one functional group selected from a hydroxyl group, a carboxyl group, and an amino group. Here, the hydroxyl group may be derived from a silanol group or may be other groups. When these functional groups are present in the particles, the compatibility of the particles with an alkaline developer is improved. Among them, hydroxyl groups and carboxyl groups are more preferred in terms of ease of introduction of functional groups into the particle shell.
[0078] These functional groups can be identified by measuring and analyzing the dry powder of the particles using a Fourier transform infrared spectrometer (FT-IR).
[0079] The particles may be surface-treated with an organosilicon compound. The organosilicon compound is preferably one having the above-mentioned functional group. For example, one represented by the following formula (8) can be mentioned. When the particles are surface-treated with such an organosilicon compound, they show high dispersibility in a dispersion liquid of the particles, a coating liquid for forming a resist film, or a resin, and a sharp pattern can be obtained.
[0080] R n -SiX 4-n ...Equation (8) (In the formula, R represents an unsubstituted or substituted hydrocarbon group having 1 to 10 carbon atoms, and may be the same or different. Examples of the substituent include an alkyl group, a vinyl group, an epoxy group, an acryloyl group, a (meth)acryloyl group, an alkoxy group, a mercapto group, a glycidoxy group, a carboxyl group, an amino group, a phenyl group, and a phenylamino group. X represents an alkoxy group having 1 to 4 carbon atoms, a hydroxyl group, or a hydrogen atom, and n represents an integer of 0 to 4.)
[0081] Specific examples include the organosilicon compounds shown in Table 1. Among them, organosilicon compounds containing at least one of an alkyl group, an epoxy group, an acryloyl group, and a (meth)acryloyl group are more preferable because they have a high bond strength with the resin.
[0082] [Table 1]
[0083] The carbon content of the particles can be measured by a carbon-sulfur analyzer. For example, the organic silicon compound surface-treated on the particles is separated from the unreacted organic silicon compound by centrifugation. Only the particles surface-treated with the organic silicon compound are taken out and dried to obtain a particle powder, which is then measured to determine the carbon content of the particles.
[0084] The carbon content of the particles is preferably 3.0% by mass or less. When the carbon content is in this range, the particles have good dispersibility in a dispersion liquid and high compatibility with an alkaline developer, so that a resist film having excellent developability can be obtained.
[0085] Here, even if the carbon content exceeds 3.0% by mass, the dispersibility and stability are not improved, and a sharp pattern is not easily obtained. Rather, excessive bonding with the resin may cause development to become difficult, or the compatibility with the alkaline developer may decrease, causing particle-derived residues to occur on the substrate. The lower limit of the carbon content is not particularly set, but is, for example, 0.1% by mass. If the carbon content is less than 0.1% by mass, it may be difficult to obtain sufficient dispersibility and stability in the coating liquid for forming a resist film or in the resin. When such particles are used in a resist film, bonding with the resin may be insufficient, causing pattern roughness. This carbon content is more preferably 0.1 to 2.5% by mass, and even more preferably 0.1 to 2.0% by mass.
[0086] This carbon content varies depending on the structure and amount of the surface-treated organosilicon compound. It is preferable that this carbon content is derived from the functional group contained in the particle shell. Here, for example, when the raw material used to prepare the "original particles" before surface treatment with the organosilicon compound does not depend on the organosilicon compound, and the organosilicon compound of formula (8) is used as a surface treatment agent for the original particles, the above-mentioned preferable carbon content of 0.1 to 3.0 mass% is calculated by adding the organosilicon compound as a solid content (R n -SiO (4-n) / 2 The surface-treated particles contain about 0.2 to 7.5 parts by mass of silicon monoxide as the organic silicon compound raw material for preparing the "original particles." Examples of the organic silicon compound raw material for preparing the "original particles" include alkoxysilanes such as tetramethoxysilane (TMOS), tetraethoxysilane (TEOS), and phenyltrimethoxysilane.
[0087] Here, if the amount of the organic silicon compound contained in the surface-treated particles is less than 0.2 parts by mass relative to 100 parts by mass of the original particles, sufficient dispersibility and stability cannot be obtained, and when the particles are used in a resist film, the bond with the resin is insufficient, which may cause pattern roughness. In addition, since the solvent of the resist solution forming the upper resist film easily penetrates into the interface between the particles and the resin in the pattern film, the particles are likely to detach from the pattern part, and residues may be generated. On the other hand, even if the amount of the above-mentioned organic silicon compound exceeds 7.5 parts by mass, the dispersibility and stability are not further improved, and a sharp pattern is not easily obtained. Rather, there is a risk that excessive bonding with the resin makes it difficult to develop, or compatibility with the alkaline developer is reduced, and particle-derived residues may be generated on the substrate. The amount of the surface treatment is more preferably 0.2 to 6.0 parts by mass, and even more preferably 0.2 to 4.5 parts by mass. Incidentally, when the "original particles" are prepared using an organosilicon compound as a raw material, the "original particles" contain carbon, and therefore, in order to obtain the target carbon content of the particles of the present invention, the solid content of the organosilicon compound introduced into the particles as a surface treatment agent is reduced according to the carbon content of the "original particles" compared to the case where "original particles not containing carbon" are surface treated.
[0088] The carbon content of this particle is R A , the number density of silanol groups on the particle surface calculated by the Sears measurement method described above is R B Then, (R B / R A ) is preferably 0.2 to 25. If this value is within this range, high dispersibility in the particle dispersion, in the coating liquid for forming a resist film, and in the resin, high binding property with the resin, and high compatibility between the particle and the alkaline developer can be obtained without excess or deficiency.
[0089] Here, if this value is less than 0.2, the compatibility with the alkaline developer is low, so that the pattern may be roughened or particle-derived residue may be generated on the substrate. Conversely, if this value exceeds 25, the bond with the resin may be insufficient, so that the bond with the resin may be weak and the pattern formation itself may be difficult. In addition, the solvent of the resist solution forming the upper resist film easily penetrates into the interface between the particles and the resin in the pattern film, so that the particles are easily detached from the pattern part, and there is a possibility that residue may be generated. This value is more preferably 0.5 to 15, and even more preferably 1.0 to 10.
[0090] The particles may contain elements belonging to alkali metals and alkaline earth metals and ammonia as impurities. If any one of these elements is present in a large amount, the particles may aggregate, reducing the stability of the dispersion or coating liquid. As a result, the resist film may have pattern roughness. The total content of elements belonging to alkali metals and alkaline earth metals, when expressed as oxides, is preferably less than 100 ppm, more preferably less than 10 ppm, relative to the particles. Ammonia is NH 3 The content of the alkali metals is preferably less than 1000 ppm, more preferably less than 100 ppm, relative to the particles. The alkali metals are Li, Na, K, Rb, Cs, and Fr, and the alkaline earth metals are Be, Mg, Ca, Sr, Ba, and Ra.
[0091] In addition, the particles may contain U, Th, Pd, Ag, Mn, Mo, Ni, and Cr as impurities. If the content of these elements is high, the dispersion may be colored, or the desired refractive index of the resist film or pattern roughness may occur. Among these elements, the content of each of U and Th is preferably less than 0.3 ppb when the element is expressed as an oxide, and the total content of each of the other elements is preferably less than 100 ppm when the element is expressed as an oxide.
[0092] In addition, when the particles are used in semiconductor circuits such as highly integrated logic and memory, which require high purity, and optical sensors, the total content of these elements belonging to alkali metals and alkaline earth metals, and elements such as Pd, Ag, Mn, Mo, Ni, and Cr that are not fixed in the particles is preferably less than 0.1 ppm when expressed as an oxide. In addition, the total content of the above-mentioned elements such as Al, As, B, Bi, Cd, Co, Fe, Ga, Ge, In, Pb, Sb, Sn, Ti, V, Zn, and Zr that are not fixed in the particles is preferably less than 0.1 ppm when expressed as an oxide. If the content of these elements is 0.1 ppm or more, the metal elements may cause insulation failure of the circuit, short the circuit, or reduce the light transmittance. This may cause a decrease in the dielectric constant of the insulating film, an increase in the impedance of the metal wiring, a delay in the response speed, an increase in power consumption, etc. In particular, U and Th are undesirable because they generate radioactivity and, even if present in trace amounts, can cause semiconductors to malfunction due to the radioactivity.
[0093] In order to obtain particles with a low content of such metal impurities, there is a method of removing the metal impurities from the particles. Specifically, there are washing with acid or alkali, ion exchange, filter removal, etc. In addition, it is preferable that the material of the equipment used for manufacturing the particles does not contain these elements and has high chemical resistance. For example, plastics such as Teflon (registered trademark), FRP, carbon fiber, and alkali-free glass are preferable. In addition, it is preferable to refine the raw materials used by distillation, ion exchange, and filter removal.
[0094] The dispersion medium and concentration of the dispersion liquid are not particularly limited as long as the particles are stably dispersed in the liquid without causing aggregation or precipitation.
[0095] Examples of the dispersion medium include water, alcohols, esters, glycols, ethers, ketones, and aprotic polar solvents. These may be used alone or in combination of two or more. In particular, for resist materials, the dispersion medium is one that has a solubility parameter (SP value) of 10 or more and contains at least one organic solvent with a boiling point of more than 100° C. under atmospheric pressure, taking into consideration the workability of the resist material. Here, if the SP value is less than 10, the particles have low dispersibility and may aggregate. In addition, if the organic solvent has a boiling point of 100° C. or less, the drying during application is fast and a film is formed before leveling, so that defects such as particle-derived aggregates may occur in the coating film.
[0096] Examples of organic solvents having an SP value of 10 or more and a boiling point exceeding 100° C. include propylene glycol monomethyl ether (PGME), propylene glycol monomethyl ether acetate (PGMEA), ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-normal butyl ether, acetylacetone, ethylene glycol, diphenyl ether, glycerol, formamide, benzyl alcohol, N-methylpyrrolidone, glycerin, cyclohexanone, diethylene glycol monoethyl ether, ethylene glycol monophenyl ether, γ-butyrolactone, diethyl phthalate, dimethyl phthalate, dimethyl sulfoxide, 4-hydroxy-4-methyl-2-pentanone, 1-butanol, 2-butanol, 1,3-butanediol, 1,4-butanediol, and 1,4-dioxane. Among these, PGME, PGMEA, and γ-butyrolactone are preferred for resist applications.
[0097] The concentration of the dispersion liquid is preferably 1 to 40% by mass in terms of the solid content of the particles. If the solid content is less than 1% by mass, the processing time may be long when producing the coating liquid. Conversely, if the solid content exceeds 40% by mass, the stability of the dispersion liquid may decrease. The concentration of the dispersion liquid is more preferably 5 to 35% by mass, and further preferably 10 to 30% by mass.
[0098] [Method of manufacturing particle dispersion liquid] The method for producing a particle dispersion according to the present invention includes a first step of preparing an alkaline aqueous solution, a second step of simultaneously adding a solution of a silicon-containing compound and an aqueous solution of an alkali-soluble compound of an inorganic element other than silicon to the first step to prepare a dispersion of composite oxide particles a, and a third step of simultaneously adding a molar ratio (MOx / SiO 2 a third step of adding a solution of a compound containing silicon and an aqueous solution of an alkali-soluble compound of an inorganic element other than silicon to prepare a dispersion of composite oxide particles b; a fourth step of adding an acid to the dispersion of composite oxide particles b to remove at least a portion of the elements other than silicon that constitute the composite oxide particles b to prepare a dispersion of silica-based particles; and a fifth step of heating the dispersion of silica-based particles to 60 to 200°C, and then cooling it to less than 50°C.
[0099] In the second step, the oxide of silicon is SiO 2 When expressed as above, the concentration of the solution of a compound containing silicon is SiO 2 The concentration of the aqueous solution of an alkali-soluble compound of an inorganic element other than silicon is 3.1 to 10.0 mass% when the oxide of an inorganic element is represented as MOx. The concentration of the aqueous solution of an alkali-soluble compound of an inorganic element other than silicon is 3.1 to 10.0 mass% as MOx. The addition of these liquids is carried out so as to provide a period during which the solid concentration of the dispersion liquid is 2.5 mass% or more.
[0100] In the third step, the average primary particle diameter of the composite oxide particles b is set to 15 to 150 nm, and the value obtained by subtracting the average primary particle diameter of the composite oxide particles a from this average primary particle diameter and dividing the result by 2 is set to 3 to 14 nm. This makes it easy to adjust the average particle diameter and refractive index of the desired particles.
[0101] The particles produced in this way have a low refractive index, the number density of silanol groups on the particle surface is within a specific range, and a high aspect ratio. When these particles are used in a resist film, there is little particle detachment during pattern formation, high developability can be achieved, and the same effect can be achieved when forming an upper resist film. Each process is described below.
[0102] [First step] First, an alkaline aqueous solution is prepared. Here, the alkaline aqueous solution preferably contains an element that becomes an amphoteric oxide. The element that becomes an amphoteric oxide means that an oxide containing the element dissolves in an acid with a pH of 3 or less and dissolves in an alkali with a pH of 10 or more. More specifically, it contains at least one element selected from Al, As, B, Bi, Cd, Co, Fe, Ga, Ge, In, Pb, Sb, Si, Sn, Ti, V, Zn, and Zr. Among them, Al is preferable because it reacts with a compound containing silicon to easily form a composite oxide particle. Similarly, Si (silicon) is preferable because it reacts with a compound containing silicon easily. Examples of alkaline aqueous solutions containing these suitable elements include aqueous solutions of sodium aluminate, aluminum hydroxide, and sodium silicate.
[0103] The alkaline aqueous solution is not particularly limited as long as it has a pH of more than 7. When an amphoteric element is dissolved and present, the pH is preferably 10 or more. This pH is more preferably 10.5 or more, even more preferably 11 or more, and particularly preferably 11 to 13. This alkaline aqueous solution may also contain particles containing the above-mentioned "element that becomes an amphoteric oxide". If particles are contained in the alkaline aqueous solution, it is preferable because particles having a relatively uniform primary particle size are easily obtained in the end. The particles containing the "element that becomes an amphoteric oxide" in this alkaline aqueous solution preferably have an average particle size of 5 to 25 nm.
[0104] Here, if the average particle size of the particles is less than 5 nm, it is difficult to obtain the particles themselves. Conversely, if the average particle size exceeds 25 nm, the refractive index of the particles of the present invention finally obtained may not be sufficiently low, or it may be difficult to obtain a desired resist film. This average particle size is more preferably 5 to 20 nm, and even more preferably 5 to 15 nm.
[0105] The oxide-equivalent concentration of the element that becomes the amphoteric oxide in the alkaline aqueous solution is preferably less than 5.0% by mass. At this concentration, it is easy to suppress the aggregation of the particles obtained in the second step. The lower limit of this concentration is not particularly set, but from the viewpoint of stably obtaining particles with a high aspect ratio, it is, for example, 0.1% by mass. This concentration is more preferably less than 4.0% by mass, and even more preferably less than 3.5% by mass.
[0106] The ratio of the "element that becomes an amphoteric oxide" in the first step in the composite oxide particles a prepared in the second step is preferably 1 to 90 parts by mass on an oxide basis when the composite oxide particles a are taken as 100 parts by mass. If the ratio of the element that becomes an amphoteric oxide in the alkaline aqueous solution prepared in the first step is within this range, the formation of particle cavities and thinning of the outer shell are facilitated in the acid treatment in the fourth step described below, and particles with a low refractive index can be obtained.
[0107] If the ratio is less than 1 part by mass, it may be difficult to form a thin shell, and it may be difficult to obtain particles with a low refractive index. Conversely, if the ratio exceeds 90 parts by mass, the particle growth in the second step may be insufficient. This ratio is more preferably 3 to 90 parts by mass, even more preferably 10 to 70 parts by mass, and particularly preferably 20 to 50 parts by mass.
[0108] Silicon is one of the elements that can be converted into amphoteric oxides. However, if the proportion of "silicon that can be converted into amphoteric oxides" in the alkaline aqueous solution in the first step in the composite oxide particles a prepared in the second step is high, the refractive index of the particles finally obtained may be too high. Therefore, the oxide of silicon contained in the alkaline aqueous solution is converted into SiO2 When oxides of amphoteric elements other than silicon are expressed as MOx, the molar ratio (MOx / SiO 2 ) is preferably 10 or more. Since the alkaline aqueous solution may not contain silicon, the molar ratio (MOx / SiO 2 ) is not capped.
[0109] In addition, elements that are treated as impurities, such as alkali metals and alkaline earth metals, and that are not "elements that form amphoteric oxides" and are not "elements that constitute particles", are not included in the 100 parts by mass of the above complex oxide a.
[0110] [Second process] A solution of a compound containing silicon and an aqueous solution of an alkali-soluble compound of an inorganic element other than silicon are simultaneously added to the "alkaline aqueous solution containing an element that becomes an amphoteric oxide" prepared in the first step to prepare a dispersion of composite oxide particles a. Here, the oxide of silicon is SiO 2 When expressed as above, the concentration of the "solution of a compound containing silicon" is SiO 2 The concentration of the "aqueous solution of an alkali-soluble compound of an inorganic element other than silicon" is 3.1 to 10.0 mass% as MOx, when an oxide of an inorganic element other than silicon is expressed as MOx. These liquids are added so as to have a period during which the solid concentration of the dispersion of the composite oxide particles a becomes 2.5 mass% or more.
[0111] Here, the compound containing silicon may be, for example, at least one selected from the group consisting of silicates, acidic silicic acid solutions, and organic silicon compounds.
[0112] The silicate is preferably one or more silicates selected from alkali metal silicates, ammonium silicates, and silicates of organic bases. Examples of the alkali metal silicate include sodium silicate and potassium silicate. Examples of the organic base include quaternary ammonium salts such as tetraethylammonium salts, and amines such as monoethanolamine, diethanolamine, and triethanolamine. Examples of the ammonium silicate or the silicate of organic base include alkaline solutions in which ammonia, quaternary ammonium hydroxide, amine compounds, etc. are added to a silicic acid solution.
[0113] As the acidic silicic acid solution, a silicic acid solution obtained by removing the alkali by treating an aqueous alkali silicate solution with a cation exchange resin or the like can be used, and an acidic silicic acid solution having a pH of 2 to 4 is particularly preferred.
[0114] As the organosilicon compound, those in which n is 0 to 3 in the above-mentioned formula (8) are preferred.
[0115] Incidentally, in the organosilicon compound of formula (8), compounds in which n is 1 to 3 are poorly hydrophilic, so it is preferable to hydrolyze them in advance so that they can be mixed uniformly in the reaction system. Well-known methods can be adopted for the hydrolysis. When a basic catalyst such as an alkali metal hydroxide, aqueous ammonia, or amine is used as a hydrolysis catalyst, the basic catalyst can be removed after hydrolysis and the solution can be used as an acidic solution. When an acidic catalyst such as an organic acid or an inorganic acid is used to prepare a hydrolyzate, it is preferable to remove the acidic catalyst by ion exchange or the like after hydrolysis. The obtained hydrolyzate of the organosilicon compound is preferably used in the form of an aqueous solution. Here, the aqueous solution means that the hydrolyzate is not in a cloudy gel state and is transparent.
[0116] Examples of the organosilicon compound include those in which n is 0 to 3, as described in Table 1 above. Among them, the relationship between the carbon content of the particles and the number density of silanol groups on the particle surface (R B / R AIn terms of ease of adjusting the value of (R) to a desired range, for example, TMOS, TEOS, 3-methacryloxypropyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyldimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, and 8-methacryloxyoctyltrimethoxysilane are preferred.
[0117] Examples of alkali-soluble compounds of inorganic elements other than silicon include alkali metal salts or alkaline earth metal salts, ammonium salts, and quaternary ammonium salts of metal or nonmetal oxoacids that form oxides of inorganic elements other than silicon, specifically sodium aluminate, sodium tetraborate, ammonium zirconyl carbonate, potassium antimonate, potassium stannate, sodium aluminosilicate, sodium molybdate, ammonium cerium nitrate, and sodium phosphate.
[0118] These "compounds containing silicon" and "compounds of inorganic elements other than silicon" have high solubility on the alkaline side. However, when the two are mixed in the pH range where they have high solubility, the solubility of oxo acid ions such as silicate ions and aluminate ions decreases, and these compounds precipitate to form colloidal particles.
[0119] The concentrations of the solutions of "compounds containing silicon" and "alkali-soluble compounds of inorganic elements other than silicon" are SiO 2 The MOx content is 3.1 to 10.0 mass%. When the concentration is within this range, the adhesion of particles is promoted, and particles with a high aspect ratio can be obtained. The concentrations of the respective liquids may be the same or different. However, when these liquids are added, they are added so that there is a period during which the solid content concentration of the dispersion of the composite oxide particles a becomes 2.5 mass% or more.
[0120] Here, the concentration of the solution of the "silicon-containing compound" is SiO 2If the concentration is less than 3.1% by mass, the particles are inhibited from bonding together, and it may be difficult to obtain particles with a high aspect ratio. Conversely, if the concentration exceeds 10.0% by mass, the particles may aggregate together.
[0121] Furthermore, if the concentration of the aqueous solution of the "alkali-soluble compound of inorganic elements other than silicon" is less than 3.1% by mass as MOx, the particles may not adhere to each other, and it may be difficult to obtain particles with a high aspect ratio. Conversely, if the concentration exceeds 10.0% by mass, the particles may aggregate.
[0122] Here, if there is a period during which the solid content concentration of the dispersion of the composite oxide particles a is 2.5 mass% or more, the adhesion between the particles is promoted, and particles with a high aspect ratio can be obtained. This solid content concentration is preferably 2.5 to 7.0 mass%, more preferably 2.5 to 5.0 mass%, and even more preferably 2.5 to 4.0 mass%.
[0123] Here, the "period during which the solid content concentration of the dispersion of composite oxide particles a becomes 2.5 mass% or more" during the addition is not particularly limited as long as the concentration can be stably maintained, but considering the aspect ratio of the particles and the ratio (Dn / Df), it is preferable that the desired solid content concentration is reached during the period during which 10 to 90 mass% of the additive liquid is added in this step. This addition period is more preferably the period during which 20 to 90 mass% of the additive liquid is added in this step, and even more preferably the period during which 30 to 80 mass% of the additive liquid is added in this step.
[0124] In the addition of the solution in this step, the pH of the reaction system is preferably 10 or more, and the temperature is preferably 50 to 98°C. If the pH and temperature are within these ranges, the composite oxide particles a can efficiently grow by adding the "solution of a silicon-containing compound" and the "aqueous solution of an alkali-soluble compound of an inorganic element other than silicon". The pH is more preferably 10.5 or more, and even more preferably 10.5 to 13. The temperature is more preferably 65 to 98°C, and even more preferably 80 to 98°C.
[0125] Next, the molar ratio (MOx / SiO 2 ) will be explained.
[0126] If the aforementioned "alkali-soluble compounds of inorganic elements other than silicon" are expressed as oxides, a suitable example would be Al. 2 O 3 , As 2 O 3 , B 2 O 3 , Bi 2 O 3 , CdO, CoO, Fe 2 O 3 , Ga 2 O 3 , GeO 2 , In 2 O 3 , PbO, Sb 2 O 3 , SnO 2 , TiO 2 , VO, ZnO 2 , and ZrO 2 Examples of the compound oxides of inorganic elements other than silicon include zinc oxide alumina and indium tin oxide. These oxides are called MOx, and the number of moles is used to calculate the molar ratio. If multiple types of these oxides are present in the reaction system, the total number of moles of each oxide is used. The aforementioned "compounds containing silicon" are also referred to as SiO 2 The number of moles when expressed as is used in calculating the molar ratios herein.
[0127] The molar ratio in the second step is calculated including the "element that becomes an amphoteric oxide" used in the first step.
[0128] In addition, alkali metals and alkaline earth metals are not "elements that make up particles" but are treated as impurities, so they are not included in the above MOx.
[0129] These points will be similarly addressed in the third step described below.
[0130] In the second step, the addition of the "solution of a compound containing silicon" and the "aqueous solution of an alkali-soluble compound of an inorganic element other than silicon" is performed at a molar ratio (MOx / SiO 2 It is preferable to add them simultaneously so that the molar ratio (MOx / SiO 2 ) is 0.2 to 15, the structure of the composite oxide particles is mainly a structure in which silicon and elements other than silicon are alternately bonded with oxygen interposed therebetween. That is, many structures are generated in which oxygen atoms are bonded to the four bonds of a silicon atom, and an element M other than silicon is bonded to these oxygen atoms. As a result, when removing the element M other than silicon in the fourth step described below, the shape of the composite oxide particles is not destroyed, and the silicon atoms can also be removed as silicic acid monomers or oligomers accompanying the element M.
[0131] If the molar ratio is less than 0.2, the ratio of "elements other than silicon" removed in the fourth step described below is small, so that the cavity volume of the finally obtained particles may not be sufficiently large. Conversely, if the molar ratio exceeds 15, the particle growth is suppressed, and the production efficiency until the desired average particle diameter of the composite oxide particles a is satisfied may be reduced. This molar ratio is preferably 0.4 to 10, more preferably 0.6 to 5.0.
[0132] In this way, the composite oxide particles a obtained in the second step are removed by acid treatment in the fourth step described below, forming a cavity inside the outer shell of the finally obtained particles. Therefore, the composite oxide particles a are preferably in a form that can be easily removed by acid treatment.
[0133] For example, the molar ratio (MOx / SiO 2 In the second step, when a "solution of a compound containing silicon" and an "aqueous solution of an alkali-soluble compound of an inorganic element other than silicon" are added to an "alkaline aqueous solution containing an element that becomes an amphoteric oxide" having a molar ratio (MOx / SiO 2 ) can be decreased as the addition proceeds. Thus, the molar ratio (MOx / SiO 2), the molar ratio (MOx / SiO 2 ) can be reduced. If there is a gradient in the molar ratio in the particles in this manner, then in the acid treatment in the fourth step described below, when at least a portion of the elements other than silicon that constitute the composite oxide particles b is removed, the portion corresponding to the composite oxide particles a can be efficiently removed, facilitating the formation of particle cavities and thinning of the outer shell, and thus making it possible to obtain particles with a low refractive index, which is preferable.
[0134] The composite oxide particles a are preferably adjusted so that their average particle size (Da) is approximately 10 to 145 nm.
[0135] Here, if the average particle diameter (Da) is less than 10 nm, the shell of the particles finally obtained may be thick, and the cavity volume of the particles may not be sufficiently large. Conversely, if it exceeds 145 nm, the removal of elements M other than silicon in the fourth step described below may be insufficient, and the cavity volume of the particles may not be sufficiently large, making it difficult to obtain particles with a low refractive index, or the pattern may become rough due to the large particle diameter. The average particle diameter (Da) is more preferably 15 to 115 nm, even more preferably 20 to 75 nm, and particularly preferably 20 to 50 nm.
[0136] [Third step] In this step, a smaller molar ratio (MOx / SiO 2 ) "a solution of a compound containing silicon" and "an aqueous solution of an alkali-soluble compound of an inorganic element other than silicon" are added. In this way, composite oxide particles a are grown and a dispersion of composite oxide particles b is prepared.
[0137] The composite oxide particles b are prepared so that the average particle diameter is 15 to 150 nm, and the value obtained by subtracting the average primary particle diameter of the composite oxide particles a from the average primary particle diameter of the composite oxide particles b and dividing the result by 2 is 3 to 14 nm.
[0138] The composite oxide particles b are surrounded by the composite oxide particles a and have a higher molar ratio (MOx / SiO 2 This layer is less susceptible to acid attack than composite oxide a, and therefore forms the outer shell of the final particle.
[0139] The silicon-containing compound and the alkali-soluble non-silicon inorganic element compound used in the third step are selected from those exemplified in the second step. These compounds may be the same type as those used in the second step, or may be different types from those exemplified in the second step.
[0140] The molar ratio (MOx / SiO 2 ) in the third step (MOx / SiO 2 ) is B, the ratio (B / A) is preferably less than 0.40. If the ratio (B / A) is less than 0.40, the silica component in the surface layer of the composite oxide particles is increased, and the formation of the shell is facilitated. As a result, even if elements other than silicon are removed in the fourth step described below, the shape of the composite oxide particles is not destroyed, and hollow silica particles can be stably obtained. If the ratio (B / A) is 0.40 or more, it is difficult to form an outer shell containing a large amount of silica components, so that the composite oxide particles are destroyed when elements other than silicon are removed in the fourth step, making it difficult to maintain the particle shape. For this reason, there is a risk that it may be difficult to obtain hollow silica particles. The ratio (B / A) is more preferably 0.30 or less, and even more preferably 0.20 or less.
[0141] The composite oxide particles b after the addition are adjusted so that their average particle size (Db) is 15 to 150 nm.
[0142] Here, if the average particle size (Db) is less than 15 nm, the porosity of the particles will be small, and it may be difficult to obtain a film with a low refractive index. Conversely, if it exceeds 150 nm, the particle size will be large, and there is a risk of pattern roughness occurring, the transparency of the coating film may be insufficient due to particle scattering, and the haze may be insufficient. The average particle size (Db) is preferably 20 to 120 nm, more preferably 25 to 80 nm, and particularly preferably 25 to 55 nm.
[0143] Moreover, the value (Dc) obtained by dividing the difference between the average particle size (Db) and the average particle size (Da) by 2 is adjusted to be 3 to 14 nm.
[0144] Here, if the difference (Dc) is less than 3 nm, the shell finally obtained may be too thin, making it difficult to maintain the particle shape. Conversely, if the particle is more than 14 nm, the refractive index may not be sufficiently low, making it difficult to obtain a desired resist film, or metal impurities may not be sufficiently removed. The difference (Dc) is more preferably 3 to 10 nm, and further preferably 3 to 6 nm.
[0145] The ratio (Dc / Db) is preferably from 0.03 to 0.35. When this ratio is in this range, a resist film with a low refractive index can be obtained.
[0146] Here, if this ratio is less than 0.03, it may be difficult to obtain the strength required to maintain the particle shape, and therefore it may be difficult to obtain the particles themselves. Conversely, if the ratio exceeds 0.35, the refractive index of the particles may not be sufficiently low, and therefore it may be difficult to obtain the desired resist film. The ratio (Dc / Db) is more preferably 0.04 to 0.28, and even more preferably 0.05 to 0.20.
[0147] The dispersion of composite oxide particles a used in this step preferably has a pH of 10 or more.
[0148] The concentrations of the solutions of "compounds containing silicon" and "alkali-soluble compounds of inorganic elements other than silicon" are SiO 2 Preferably, the concentration is 0.05 to 3.0 mass % in terms of MOx. When the concentration is within this range, aggregation of the composite oxide particles a obtained in the second step is suppressed, and monodisperse particles can be obtained.
[0149] In the addition of the solution in this step, the pH of the reaction system is preferably 10 or more, and the temperature is preferably 50 to 98°C. If the pH and temperature are within these ranges, the composite oxide particles b can be efficiently grown by adding the "solution of a silicon-containing compound" and the "aqueous solution of an alkali-soluble compound of an inorganic element other than silicon". The pH is more preferably 10.5 or more, and even more preferably 10.5 to 13. The temperature is more preferably 65 to 98°C, and even more preferably 80 to 98°C.
[0150] [Fourth step] In this step, an acid is added to the dispersion of composite oxide particles b to remove at least a portion of the elements other than silicon that constitute composite oxide particles b, thereby preparing a dispersion of silica-based particles. The elements are removed, for example, by dissolving them using a mineral acid or an organic acid, by contacting them with a cation exchange resin to remove them by ion exchange, or by a combination of these methods.
[0151] The concentration of the composite oxide particles b in the dispersion liquid differs depending on the treatment temperature, but is preferably 0.1 to 30 mass % in terms of the composite oxide particles b converted into oxide.
[0152] Here, if the concentration is less than 0.1% by mass, the amount of dissolved silica increases, which may make it difficult to maintain the shape of the composite oxide particles. In addition, the treatment efficiency is low due to the low concentration. Conversely, if the concentration is higher than 30% by mass, the dispersibility of the particles may be insufficient. In addition, in the case of composite oxide particles having a high content of elements other than silicon, it may be difficult to remove the elements other than silicon uniformly or efficiently. The concentration of the dispersion of composite oxide particles b is more preferably 0.5 to 25% by mass.
[0153] The removal of the above elements is achieved by adjusting the molar ratio of the resulting particles (MOx / SiO 2 ) is preferably continued until it becomes 0.03 or less.
[0154] Here, the molar ratio (MOx / SiO 2 If the molar ratio (MOx / SiO) is greater than 0.03, it may be difficult to obtain the refractive index of the hollow silica particles finally obtained and the strength required to maintain the particle shape. 2 ) is more preferably 0.01 or less.
[0155] The dispersion of silica-based particles from which at least a part of the elements other than silicon has been removed can be washed by a known washing method such as ultrafiltration as necessary. At least a part of the dissolved elements other than silicon is removed by washing. In this case, if a part of the alkali metal ions and the like in the dispersion is removed in advance and then ultrafiltration is performed, a dispersion of silica-based particles with high dispersion stability can be obtained.
[0156] In addition, this dispersion from which "at least a portion of the elements other than silicon have been removed" can also be contacted with at least one of a cation exchange resin and an anion exchange resin to remove a portion of the dissolved elements other than silicon, alkali metal ions, etc. When washing, heating the solution can be used for effective washing.
[0157] By washing in this manner, it is possible to effectively reduce the content of impurities such as alkali metals in the particles obtained by heat-treating the silica-based particles in the fifth step. The content of these impurities corresponds to the content of the impurities in the particles described above.
[0158] If the content of impurities in the silica-based particles is within the range of impurities in the particles described above, washing in this step is not particularly required.
[0159] [Fifth step] In this step, the dispersion liquid of the silica-based particles obtained in the fourth step is heated to 60 to 200°C, and then cooled to less than 50°C.
[0160] In this way, the silica-based particle dispersion is heated to dissolve the silicon from the silica-based particles, and then the temperature of the dispersion is lowered to fix the dissolved silicon to the silica-based particles, thereby obtaining the particles of the present invention.
[0161] Here, if the heating temperature is less than 60°C, the silicon content in the particles will not dissolve sufficiently, and the particles may not be fixed in the shape of hollow particles. Conversely, if the temperature exceeds 200°C, the silicon content in the particles will dissolve excessively, the outer shell will dissolve, and the hollow shape may collapse. After heating to the target temperature, the temperature may be immediately lowered, but in order to produce stably, it is preferable to maintain the temperature for 30 minutes or more. The heating temperature is preferably 70 to 180°C, more preferably 80 to 160°C.
[0162] In heating the dispersion, the heating rate is preferably 5.0° C. / min or less. At such a heating rate, the sudden dissolution of the silicon content in the particles is suppressed, and the shape of the hollow particles is easily maintained. Therefore, the desired properties such as the refractive index of the particles of the present invention are easily obtained stably. The lower limit of this heating rate is not particularly set, but is, for example, 0.3° C. / min. If the heating rate is extremely slow, it takes too long to raise the temperature to the target temperature, which may result in low production efficiency. The heating rate is preferably 0.5 to 4.0° C. / min, more preferably 0.8 to 3.0° C. / min.
[0163] After heating the dispersion liquid, the temperature is lowered to less than 50° C. By lowering the temperature to less than 50° C., the dissolved silicon content can be easily fixed to the silica-based particles. The temperature may be lowered to room temperature to facilitate handling.
[0164] The particle dispersion thus obtained satisfies the above-mentioned particle properties, and when the particles are used in a resist film, a low refractive index and excellent developability can be achieved.
[0165] [Particle surface treatment] In the present invention, after the fifth step, an organosilicon compound may be added to perform surface treatment of the particles. As the organosilicon compound to be used, it is preferable to use an organosilicon compound represented by the above formula (8) in which n is 1 to 3. Here, when an organosilicon compound in which n is 0 is used, it is preferable to use a partial hydrolyzate of the organosilicon compound. This makes it possible to adjust the number density of silanol groups on the particle surface calculated by the Sears measurement method. In addition, the introduction of a functional group improves the compatibility between the particles and the resin component, which is preferable in terms of obtaining particles with high dispersibility in the coating liquid and film. The organosilicon compounds may be used alone or in combination.
[0166] The method of surface treatment of particles is to first prepare a dispersion liquid of particles. As the dispersion medium, it is preferable to use alcohols such as methanol and ethanol. A predetermined amount of an organosilicon compound represented by formula (8) is added to the dispersion liquid, and the organosilicon compound is hydrolyzed. Water can be added to this hydrolysis as necessary. The ratio (Mw / Mo) of the number of moles of water (Mw) to the number of moles of the organosilicon compound (Mo) used is preferably 1 or more.
[0167] Here, if the ratio (Mw / Mo) is less than 1, hydrolysis may be insufficient, and the transparency and haze of the coating may be insufficient. There is no particular upper limit for this ratio, but if this ratio exceeds 500, the hydrolysis reaction may become intense, and the organosilicon compounds may polymerize with each other, making it difficult to efficiently treat the particle surface with the organosilicon compound. This ratio is more preferably 1 to 100.
[0168] In this hydrolysis, an acid or alkali can be used as a hydrolysis catalyst, if necessary. Among them, ammonia is preferred. This is because if ammonia is used, it is easy to remove even if it remains in the dispersion, and the stability of the dispersion is easily maintained. The number of moles of ammonia used (M N ) and the mole number (Mo) of the organosilicon compound (M N / Mo) is preferably in the range of 0.05 to 50.
[0169] Here, the ratio (M N If the ratio (R / Mo) is less than 0.05, the hydrolysis may be insufficient, and the transparency and haze of the coating may be insufficient. If the ratio exceeds 50, the hydrolysis reaction may become too vigorous, and the organosilicon compounds may polymerize with each other, making it difficult to efficiently treat the particle surfaces with the organosilicon compounds. This ratio is more preferably 0.1 to 10.
[0170] The surface treatment is preferably carried out in a homogeneous system, and in order to promote the reaction between the particles and the organosilicon compound, it is preferable to heat the particles at a temperature below the boiling point of the dispersion medium (for example, room temperature to 120° C.) for 0.5 to 48 hours.
[0171] When the particles, whose surfaces are chemically bonded to the organosilicon compound by this surface treatment, are used in a resist material, the particles have high dispersibility in the film, making it easy to obtain a sharp pattern.
[0172] Examples of the organosilicon compound include those shown in Table 1. The particles may contain one or more of these organosilicon compounds. In the surface treatment, the particles may be treated with one or more of these organosilicon compounds, or may be treated in stages with the same type, a mixture of multiple types, or multiple types separately.
[0173] The amount of this organosilicon compound is 100 parts by mass of the "original particles" before surface treatment. n -SiO (4-n) / 2 ) is preferably 0.2 to 7.5 parts by mass.
[0174] Here, if the amount is less than 0.2 parts by mass, the bond with the resin is insufficient. Therefore, the bond with the resin is weak, and it may be difficult to form a pattern. On the other hand, if the amount is more than 7.5 parts by mass, the compatibility with the alkaline developer is low, and therefore, the pattern may be roughened or particle-derived residue may be generated on the substrate. The amount of the organosilicon compound is more preferably 0.2 to 6.0 parts by mass, and even more preferably 0.2 to 4.5 parts by mass.
[0175] The amount of surface treatment should be such that only a desired amount of organosilicon compound is reacted with the particle surface and the carbon content of the finally obtained particles is within the range. This carbon content varies depending on the structure and amount of the chemically bonded organosilicon compound. Here, when the raw material used to prepare the "original particles" before surface treatment does not depend on the organosilicon compound, and the organosilicon compound of formula (8) is used as a surface treatment agent for the "original particles", the aforementioned carbon content of 0.1 to 3 mass% is calculated by adding the organosilicon compound to 100 parts by mass of the "original particles" as a solid content (R n -SiO (4-n) / 2 ) is surface-treated in an amount of about 0.2 to 7.5 parts by mass. Of course, when an organosilicon compound is used to prepare the "original particles" and the carbon content is present in the "original particles", the carbon content is also added to the carbon content of the particles finally obtained. Therefore, the amount of solid content of the organosilicon compound that is surface-treated to obtain the target carbon content of the particles of the present invention is reduced according to the carbon content of the "original particles" compared to the case where the surface treatment is performed on "original particles not containing carbon".
[0176] The physical properties and preferred ranges of the finally obtained particles and their dispersion are the same as those of the above-mentioned particles and their dispersion.
[0177] [Coating liquid for film formation] The particles of the present invention can be applied to a coating liquid for forming a coating film. This coating liquid contains particles, a matrix forming component, and a dispersion medium. This dispersion medium contains at least one of water and an organic dispersion medium. In addition to these, the coating liquid may contain additives such as a polymerization initiator, a leveling agent, and a surfactant.
[0178] The concentration of particles in the coating liquid is preferably 5 to 95% by mass as solid content based on the total amount of solid content of the particles, matrix forming components, etc. contained. If the particle concentration is less than 5% by mass, it may be difficult to sufficiently reduce the refractive index of the coating. Conversely, if it is more than 95% by mass, cracks may occur in the coating, the surface unevenness may become large, pattern roughness may occur, and transparency and haze may deteriorate. The particle concentration is more preferably 20 to 90% by mass, and even more preferably 35 to 85% by mass.
[0179] The matrix-forming component preferably contains an alkali-soluble group.
[0180] Examples of the alkali-soluble group include a hydroxyl group, a phenolic hydroxyl group, a carboxyl group, a fluorinated alcohol group, a sulfonimide group, a bis(alkylcarbonyl)methylene group, and an alkylene oxide group.
[0181] Examples of the matrix-forming component containing an alkali-soluble group include polycondensates of organosilicon compounds, ultraviolet-curable resins, thermosetting resins, and thermoplastic resins.
[0182] Here, examples of the ultraviolet-curable resin include (meth)acrylic resin, urethane resin, and vinyl resin.
[0183] Examples of the thermosetting resin include urethane resin, melamine resin, silicon resin, butyral resin, reactive silicone resin, phenol resin, epoxy resin, unsaturated polyester resin, and thermosetting acrylic resin.
[0184] Examples of the thermoplastic resin include polyester resin, polycarbonate resin, polyamide resin, polyphenylene oxide resin, thermoplastic acrylic resin, vinyl chloride resin, fluororesin, vinyl acetate resin, and silicone rubber.
[0185] These resins may be copolymers or modified products of two or more kinds, or may be used in combination. Furthermore, these resins may be emulsion resins, water-soluble resins, or hydrophilic resins.
[0186] The components forming these resins are preferably monomers or oligomers in view of particle dispersibility and ease of coating.
[0187] The concentration of the matrix-forming component in the coating liquid is preferably 5 to 95% by mass in terms of solid content with respect to the total amount of solid content of the particles, matrix-forming component, and the like contained therein.
[0188] Here, if the concentration of the matrix-forming component is less than 5% by mass, it is difficult to form a film. Even if a film is obtained, there is a possibility that cracks will occur in the film, that the surface irregularities will become large, that pattern roughness will occur, and that transparency, haze, etc. will deteriorate. On the other hand, if it is more than 95% by mass, the amount of particles will be small, so that it may be difficult to sufficiently reduce the refractive index. The concentration of this matrix-forming component is more preferably 10 to 80% by mass, and further preferably 15 to 65% by mass.
[0189] As the organic dispersion medium, one that can uniformly disperse particles and dissolve or disperse additives such as matrix forming components and polymerization initiators is used. Among them, hydrophilic dispersion media and polar dispersion media are preferred. As shown in Table 2, examples of hydrophilic dispersion media include alcohols, esters, glycols, and ethers. Examples of polar dispersion media include esters, ketones, and aprotic dispersion media. These may be used alone or in combination of two or more.
[0190] [Table 2]
[0191] Any additive that can be used in the past for film formation can be used as the additive. For example, a polymerization initiator, a leveling agent, etc. can be used to promote polymerization of the matrix-forming components and improve film-forming properties.
[0192] Examples of the polymerization initiator include those shown in Table 3.
[0193] [Table 3]
[0194] Examples of the leveling agent include acrylic leveling agents, silicone leveling agents, fluorine leveling agents, nonionic leveling agents, cationic leveling agents, and anionic leveling agents. These may be used alone or in combination of two or more. The content of the leveling agent is preferably 0.001 to 1.0% by mass in 100% by mass of the non-volatile components of the dispersion. By containing a leveling agent in this range, it becomes easy to obtain a film with excellent coatability and small surface unevenness.
[0195] Regarding the concentration of these additives in the coating liquid, those contained as solids when the coating is formed are counted as matrix forming components for convenience, and after coating, they are counted as the matrix.
[0196] The solid content concentration of the coating liquid (the ratio of the total solid content of the particles and the solid content of the matrix-forming components to the coating liquid) is preferably 0.1 to 60% by mass.
[0197] Here, if the solid content concentration of the coating liquid is less than 0.1% by mass, it may be difficult to obtain a desired film thickness, or the processing time required for manufacturing the coated substrate may be long, resulting in a decrease in productivity. Conversely, if it is more than 60% by mass, the stability of the coating liquid may decrease. In addition, the viscosity of the coating liquid may increase, resulting in a decrease in coatability. The solid content concentration of the coating liquid is more preferably 1 to 50% by mass.
[0198] [Coated base material] The coating solution is used to form a coating on a substrate.
[0199] Specifically, a coating liquid is applied onto a substrate, and then dried to form a coating film on the substrate. The coating film is then irradiated (exposed) to ultraviolet light or the like, and developed to form a pattern in a desired shape. The pattern is preferably formed by wet etching.
[0200] The method of applying the coating liquid is not particularly limited as long as it can form a coating on the substrate. For example, well-known methods such as spraying, spin coating, roll coating, dip coating, and bar coating can be used. Drying is performed, for example, by heating to about 50 to 150°C to evaporate and remove the dispersion medium. Exposure is performed through a mask. Examples of actinic rays or radiation that can be applied to this exposure include ArF light, KrF light, F 2 Examples of the light that can be used for the coating include light, extreme ultraviolet rays, vacuum ultraviolet rays, electron beams, X-rays, soft X-rays, infrared light, g-rays, h-rays, and i-rays. The exposed areas of the coating are then patterned using an alkaline developer. The coating is mainly composed of particles and a matrix.
[0201] In the case of a coating, the ratio of the particles and the solid content of the matrix-forming components in the coating liquid is the same as the ratio of the particles and the matrix in the coating. As mentioned above, the additives in the coating liquid that remain as solids are counted as the matrix.
[0202] The thickness of the coating is preferably, for example, 50 to 250 nm for an anti-reflection coating, and 500 nm to 5 μm for a resist coating.
[0203] The alkaline developer may be either an inorganic or organic alkaline compound.
[0204] Examples of inorganic alkaline compounds include sodium hydroxide, potassium hydroxide, sodium silicate, potassium silicate, sodium carbonate, potassium carbonate, and ammonia. Examples of organic alkaline compounds include tetramethylammonium hydroxide (TMAH), 2-hydroxyethyltrimethylammonium hydroxide, monomethylamine, dimethylamine, trimethylamine, monoethylamine, diethylamine, triethylamine, monoisopropylamine, diisopropylamine, and ethanolamine. These inorganic and organic alkaline compounds may be used alone or in combination of two or more. The concentration of the alkaline compound in the alkaline developer is preferably 0.01 to 5% by mass.
[0205] The refractive index of the coating is preferably 1.15 to 1.40.
[0206] Here, it is difficult to obtain a coating with a refractive index of less than 1.15. Conversely, if the refractive index exceeds 1.40, it may be difficult to obtain high developability during pattern formation, although this depends on the refractive index of the substrate or the refractive index of other films formed under the coating as required. The refractive index of the coating is more preferably 1.15 to 1.35, and even more preferably 1.15 to 1.30.
[0207] The light transmittance of the coated substrate is preferably 80.0% or more. If the light transmittance is less than 80.0%, the curing of the coating may be non-uniform, and it may be difficult to obtain high developability during pattern formation. The light transmittance is more preferably 85.0% or more, and even more preferably 90.0% or more.
[0208] The haze of the coated substrate is preferably 1.5% or less, more preferably 1.2% or less, and even more preferably 0.8% or less.
[0209] Furthermore, the surface irregularities of the pattern of the coated substrate are preferably less than 5 nm.
[0210] Here, if the surface unevenness is 5 nm or more, there is a risk that the pattern will become rough during development, or that the pattern edges will have jagged shapes, making it difficult to obtain a sharp pattern. The surface unevenness is more preferably less than 4 nm, and even more preferably less than 3 nm.
[0211] In addition, it is preferable that the linearity of the pattern of the coated substrate is such that no "jagged edges" are observed at the pattern edges. Here, if "jagged edges" exist at the pattern edges, there is a risk of adversely affecting the circuit pattern in a later process or of crosstalk occurring between patterns.
[0212] It is also preferable that no residues derived from silica particles are present on the coated substrate, since the presence of residues on the substrate may adversely affect the circuit pattern in a later process or cause crosstalk between patterns.
[0213] In addition, as a method for evaluating pattern roughness and residues after the formation of the upper resist film, the pattern film was immersed in PGME, which is the main solvent of the resist solution, and the surface unevenness, linearity, and residues on the substrate of the pattern were evaluated. The surface unevenness of the pattern of the coated substrate after the solvent resistance test is preferably less than 5 nm. In addition, it is preferable that the linearity of the pattern after the solvent resistance test is such that no "jagged edges" are observed at the pattern edges. Furthermore, it is preferable that there is no residue derived from silica particles on the coated substrate after the solvent resistance test.
[0214] The following describes an embodiment of the present invention.
[0215] [Example 1] <Preparation of Particle Dispersion> Pure water, Al 2 O 3 A sodium aluminate aqueous solution having a concentration of 22 mass% as a solution was added to obtain Al 2 O 3 10.0 kg of an aqueous sodium aluminate solution having a concentration of 1.0 mass % as a sodium aluminate solution and a pH of 12.6 was prepared (first step).
[0216] Next, this is heated to 80°C to form SiO 2 11.4 kg of sodium silicate aqueous solution with a concentration of 4.0 mass % as a weight percent, Al 2 O 3 3.8 kg of a sodium aluminate aqueous solution having a concentration of 4.0 mass% as a dispersion medium was added at the same time. After that, washing was performed by centrifugal sedimentation to obtain a dispersion of composite oxide particles (a1). The average particle diameter of the composite oxide particles (a1) was 30 nm (second step).
[0217] The dispersion of the composite oxide particles (a1) was heated to 95° C. to form a SiO 2 114.0 kg of sodium silicate aqueous solution with a concentration of 1.5 mass% as a solution and Al 2 O 3 38.0 kg of sodium aluminate aqueous solution having a concentration of 0.5 mass% as a solid content was added at the same time. After that, the mixture was washed using an ultrafiltration membrane, and the solid content was adjusted to 13 mass%. After that, the mixture was filtered using a capsule filter having an opening of 1 μm to obtain a dispersion of composite oxide particles (b1). The average particle diameter of the composite oxide particles (b1) was 41 nm (third process).
[0218] 11,250 g of pure water was added to 5,000 g of the dispersion of composite oxide particles (b1), and concentrated hydrochloric acid (concentration: 35.5% by mass) was added dropwise to adjust the pH to 1.0. While adding 10 L of an aqueous hydrochloric acid solution of pH 3 and 5 L of pure water, the dissolved aluminum salt was separated and washed using an ultrafiltration membrane to obtain silica-based particles (c1) with a concentration of 10% by mass (fourth step).
[0219] Next, ammonia water was added to 500 g of the dispersion of silica particles (d1) to adjust the pH of the dispersion to 10.5, and the dispersion was transferred to a pressure-resistant container, which was then heated to 140°C at a rate of 1.5°C / min and held for 10 hours, and then cooled to 25°C (fifth step).
[0220] Thereafter, ion exchange was performed for 3 hours using 800 g of a cation exchange resin (Diaion SK1B manufactured by Mitsubishi Chemical Corporation), and then ion exchange was performed for 3 hours using 400 g of an anion exchange resin (Diaion SA20A manufactured by Mitsubishi Chemical Corporation). Thereafter, ion exchange was further performed for 3 hours at 80° C. using 400 g of a cation exchange resin, followed by washing, to obtain an aqueous dispersion of particles (P1).
[0221] The solvent in this aqueous dispersion of particles (P1) was replaced with methanol using an ultrafiltration membrane to produce a methanol dispersion of particles (P1) with a solid content concentration of 20 mass %.
[0222] Surface treatment of particles with organosilicon compounds To 200 g of a methanol dispersion of the particles (P1), 0.4 g of ammonia water having a concentration of 28% by mass and 4.0 g of pure water were added, and the mixture was stirred at room temperature for 0.5 hours.
[0223] Next, 1.2 g of γ-methacryloxypropyltrimethoxysilane (KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.) was added as an organic silicon compound, and the mixture was stirred at 50° C. for 6 hours to obtain a dispersion of particles (S1) in which the particles (P1) were surface-treated. The solvent was replaced with methanol using an ultrafiltration membrane to produce a methanol dispersion of particles (S1) with a solid content concentration of 20 mass%.
[0224] In addition, the dispersion medium of the methanol dispersion of the particles (S1) was replaced with PGME using an evaporator to obtain a PGME dispersion of the particles (S1) with a solid content concentration of 20.5% by mass, which was used to produce a coating liquid for forming a resist film, as described below.
[0225] The particles and their dispersions were measured by the following methods.
[0226] The characteristics of each production step of the particles, and the properties of the particles and dispersion liquid are shown in Tables 4 to 9 (the same applies to the following Examples and Comparative Examples).
[0227] (1) Average particle size (D), shell thickness, average particle size (Da) of composite oxide particles a, and average particle size (Db) of composite oxide particles b The particle dispersion was diluted to 0.01% by mass, and then dried on a collodion film of a copper cell for an electron microscope. Next, this was photographed at a specified magnification using a field emission transmission electron microscope (HF5000, manufactured by Hitachi High-Technologies Corporation). The particle area of 300 random particles in the obtained photographic projection (TEM photograph) was calculated by image processing, and the circle equivalent diameter was calculated from the area. The average value of the circle equivalent diameters was taken as the average particle diameter (D) of the particles.
[0228] In addition, for 300 randomly selected particles, image processing was performed to determine the area of the cavity of the particle, and the equivalent circle diameter was calculated from the area. This was then subtracted from each particle diameter, and the average value obtained by dividing the result by 2 was used as the thickness of the outer shell.
[0229] Furthermore, the average particle size (Da) of the composite oxide particles a and the average particle size (Db) of the composite oxide particles b were determined in the same manner as in determining the average particle size (D) of the particles.
[0230] (2) Refractive index The particle dispersion was placed in an evaporator to evaporate the dispersion medium. It was then vacuum dried at 120°C for 24 hours to obtain a particle powder. A few drops of a standard refractive index liquid with a known refractive index were placed on a glass plate, and the powder was mixed into this. This operation was performed with various standard refractive index liquids, and the refractive index of the standard refractive index liquid when the mixed liquid became transparent was taken as the refractive index of the particles.
[0231] (3) Number density of silanol groups on the particle surface The silanol group density of the particles is calculated from the Sears number and the specific surface area, specifically, by the above-mentioned formulas (1) and (2).
[0232] The Sears number is measured by titration with NaOH according to the description in Analytical Chemistry 28 (1956), 12, 1981-1983 by Sears. Specifically, the methanol dispersion of the particles is solvent-substituted with water using an evaporator, and the aqueous dispersion of the particles is diluted with pure water so that the silica particle concentration becomes 1% by mass. 30 g of sodium chloride is added to 150 g of the diluted dispersion, and the pH is adjusted to 4.0 with hydrochloric acid. Then, 0.1 N NaOH aqueous solution is titrated at 0.1 ml / sec., and the Sears number is expressed as the amount of NaOH aqueous solution required to reach a pH of 9.0. (That is, the Sears number is the titration amount of 0.1 N NaOH aqueous solution to 1.5 g of particles.) The titration with 0.1 N NaOH aqueous solution was performed using an automatic titrator with a fixed titration speed of 0.1 ml / sec.
[0233] The specific surface area is measured by the BET method using nitrogen adsorption. The measurement sample was prepared by drying an aqueous dispersion of particles at 105°C and powdering them.
[0234] (4) Aspect ratio of particles, number ratio of particles, and aspect ratio of cavity of particles For 300 randomly selected particles in the TEM photograph taken when determining the average particle diameter (D), the ratio of the long axis of each particle to the short axis perpendicular thereto (long axis / short axis) was determined, and the average value was taken as the average aspect ratio of the particles. In addition, the number ratio of particles (N) with aspect ratios of 1.50 to 5.00 was determined. Furthermore, the average aspect ratio was determined for particles (N) with aspect ratios of 1.50 to 5.00.
[0235] In addition, the ratio of the major axis of the cavity of each of the 300 particles to the minor axis perpendicular thereto (major axis / minor axis) was calculated, and the average value was taken as the average aspect ratio of the cavity of each particle.
[0236] (5) The weighted average of the minor axis of non-connected particles and the diameter of the constricted part of connected particles (Dn), and the average primary particle diameter (Df) The weighted average of the short diameters of the non-linked particles and the diameters of the constricted parts of the linked particles was calculated for 300 random particles in the TEM photograph taken when calculating the average particle diameter (D) of the above-mentioned particles, and was designated as (Dn). The short diameters of the non-linked particles and the short diameters of the individual particles connected to the linked particles were also calculated, and the average value was designated as the average primary particle diameter (Df).
[0237] (6) Specific surface area by BET method The specific surface area was calculated from the amount of adsorbed nitrogen by the BET method using a specific surface area measuring device (Multisorb 12 manufactured by Yuasa Ionics Co., Ltd.).
[0238] (7) Specific surface area (A1) by pulsed NMR The methanol dispersion of the particles was subjected to solvent replacement with water using an evaporator to prepare an aqueous dispersion with a silica particle concentration of 10.0% by mass. The relaxation times of the dispersion and the dispersion medium were measured using a pulse NMR (Acorn Area, manufactured by Xigo nanotools), and the specific surface area (A1) was calculated from the above-mentioned formulas (3) and (4). The measurement conditions were a magnetic field of 0.3 T, a measurement frequency of 13 MHz, and a measurement nucleus of 0.5 T. 1 The H NMR measurement method was the CPMG pulse sequence method, with a sample amount of 1 ml, a Ka value of 0.000027, and a temperature of 25° C. Here, the Ka value was calculated from the above-mentioned formulas (5) to (7) by performing pulse NMR measurement at 25° C. on an aqueous dispersion prepared by replacing the solvent in a methanol dispersion of particles (P1) with water using an evaporator and adjusting the solid content concentration to 10.0 mass %, and on the aqueous dispersion medium.
[0239] (8) Specific surface area (A2) The specific surface area (A2) was calculated using the average particle diameter (D) and density (Sd) of the particles according to the above-mentioned formula (5).
[0240] (9) Density of particle in helium gas and nitrogen gas The particle dispersion was heated to 110°C and held for 3 hours to dry. The density of 3.0 g of the obtained powder was measured using a dry automatic density meter (AccuPic II1340, manufactured by Micromeritics Co., Ltd.). At this time, He and N were used as measurement gases. 2 The density of each measurement gas was measured using the following:
[0241] (10) Particle 29 Q by Si-NMR analysis 4 Percentage of the area of the peak representing the structure The particle dispersion is placed in a dedicated zirconia sample tube, and measured using a 6 mmφ sample tube probe for solids on an NMR device (Agilent Corp. VNMRS-600) using the single pulse non-decoupling method without sample rotation. Polydimethylsiloxane is used as the secondary standard, and the chemical shift is set to -34.44 ppm. The spectrum obtained is subjected to waveform separation using analysis software Origin, and the area of each peak is calculated. More specifically, 29 The area of the peak appearing at chemical shifts of -78 to -88 ppm in Si-NMR spectroscopy (Q 1 ) and the area of the peak appearing at chemical shifts of -88 to -98 ppm (Q 2 ) and the area of the peak appearing at chemical shifts of -98 to -108 ppm (Q 3 ) and the area of the peak appearing at chemical shifts of -108 to -120 ppm (Q 4 ), (Q 4 / ΣQ) × 100, where ΣQ = Q 1 +Q 2 +Q 3 +Q 4 It is.
[0242] (11) Content of metal elements and metal impurities in particles The content of metal elements (alkali metals, alkaline earth metals, Al, Co, Cr, Cu, Fe, Mn, Ni, Si, Th, Ti, U, Zn, and Zr, etc.) in the particles was measured by dissolving the particles in hydrofluoric acid, heating to remove the hydrofluoric acid, adding pure water as necessary, and measuring the resulting solution using an ICP inductively coupled plasma optical emission spectrometer (ICP-8500, manufactured by Shimadzu Corporation). Note that, for metal elements other than the above impurity elements, the total amount of metal elements other than carbon contained in the particles was calculated to be 100 parts by mass on an oxide basis.
[0243] (12) Particle shape The particle appearance of 300 randomly selected particles in the TEM photograph taken when determining the average particle diameter (D) of the particles was observed.
[0244] (13) The shape of the cavity inside the particle shell, the percentage of particles with one cavity, and the percentage of solid particles The cavity shape inside the outer shell of 300 randomly selected particles in the TEM photograph taken when determining the average particle diameter (D) of the particles was observed, and the percentage of particles with one cavity was calculated. The percentage of solid particles was also calculated.
[0245] (14) Particle porosity and density (Sd) The area of the hollow part of the particle was determined for 300 random hollow particles in the TEM photograph taken when determining the average particle diameter (D) of the particles, and the circle equivalent diameter was calculated from that area, and the average circle equivalent diameter was taken as the average cavity diameter. The shape of the particle and the cavity was assumed to be a perfect sphere, and the average volume of the particle and the average volume of the cavity were determined, and the porosity was calculated as the ratio of the average volume of the cavity to the average volume of the particle. In addition, the density of the particle (Sd) was calculated from the obtained porosity, the ratio of the constituent components of the particle, and its density.
[0246] (15) Functional groups contained in the outer shell of particles The presence or absence of functional groups contained in the particle outer shell and the type of such groups were determined by the following method.
[0247] First, the dispersion liquid was dried in an evaporator and then dried at 150° C. The dried powder was subjected to a diffuse reflection method using a Fourier transform infrared spectrometer (FT-IR) (FT / IR-6100 manufactured by JASCO Corporation) in a wave number range of 700 cm -1 ~4000cm -1 , detector: TGS, resolution: 4.0 cm -1 The measurement was performed with 50 accumulations, and the peaks were detected and the functional groups were identified by referring to the organic compound spectrum database SDBS (https: / / sdbs.db.aist.go.jp (National Institute of Advanced Industrial Science and Technology, 2021.01)).
[0248] (16) Carbon content The dispersion liquid was centrifuged for 30 minutes using a small ultracentrifuge (Hitachi Koki Co., Ltd., CS150GXL) at a temperature of 10°C and a rotation speed of 1,370,000 rpm (1,000,000 G). The precipitate in the treatment liquid was collected and vacuum dried at 120°C for 24 hours to obtain a particle powder. The carbon content of the particles in this powder was measured using a carbon-sulfur analyzer (LECO Japan Co., Ltd., CS844).
[0249] (17) Solid content of organosilicon compound having functional group The dispersion liquid was centrifuged for 30 minutes using a small ultracentrifuge (CS150GXL, manufactured by Hitachi Koki Co., Ltd.) at a temperature of 10°C and a rotation speed of 1,370,000 rpm (1,000,000 G). The precipitate from the treatment liquid was collected and vacuum dried at 120°C for 24 hours to obtain a particle powder. The mass loss of this powder before and after heating at 500°C was measured using a thermogravimetric differential thermal analyzer (TG / DTA EXSTAR6000 MSD, manufactured by Hitachi High-Tech Science Co., Ltd.), and the amount of silicon derived from the organosilicon compound was calculated from the difference with the original particle amount. Next, the solid content (R n -SiO (4-n) / 2 ) amount to determine the solid content of the organosilicon compound having a functional group.
[0250] <Production of Coating Solution for Forming Resist Film> 73.4 g of PGME, 3.0 g of an alkali-soluble UV-curable acrylic polymer (Acrit 8KQ-2001, manufactured by Taisei Fine Chemical Co., Ltd., solid content concentration 40.0% by mass), 0.05 g of 2,2-dimethoxy-1,2-diphenylethan-1-one (Omnirad 651, manufactured by IGM RESINS BV), 0.05 g of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Omnirad 819, manufactured by IGM RESINS BV), and 0.1 g of a fluorine-based leveling agent (Megafac RS-90, manufactured by DIC Corporation, solid content concentration 10% by mass) were mixed. Then, 23.4 g of a PGME dispersion of particles (S1) was mixed therewith to prepare a coating solution for forming a resist film with a solid content concentration of 6% by mass.
[0251] <Production of Resist-Coated Substrate> The resist film-forming coating solution was applied to a 2-inch square glass substrate (Corning #1737) using a spin coater, dried at 80°C for 1 minute, and then cured by irradiating an ArF excimer laser (193 nm) through a photomask (5 μm line & space pattern) using an exposure device (Nikon NSR-S302). Thereafter, a 0.3 mass% TMAH aqueous solution was sprayed to dissolve and remove the unexposed parts, and the substrate was heated at 150°C for 5 minutes to prepare a substrate with a resist coating.
[0252] The coated substrate was measured for the following items. The results are shown in Table 10 (the same applies to the following Examples and Comparative Examples). In order to make it easier to compare performance, the type of substrate, the ratio of particles and matrix in the coating, and the coating thickness were the same in each Example and Comparative Example.
[0253] (18) Film thickness and refractive index The film thickness and refractive index of the coated substrate were measured using an ellipsometer (EMS-1, manufactured by ULVAC Co., Ltd.) and the refractive index was evaluated according to the following classification. Criteria for evaluating the refractive index of coatings; ◎: 1.30 or less ○:1.31~1.35 △:1.36~1.40 ×: 1.41 or higher
[0254] (19) Total light transmittance and haze The total light transmittance and haze of the coated substrate were measured using a haze meter (NDH-5000, manufactured by Nippon Denshoku Industries Co., Ltd.) and were evaluated according to the following classification. Evaluation criteria for total light transmittance; ◎: 90% or more ○: 85%~89% △: 80%~84% ×: 79% or less Hayes's assessment criteria; ◎: 0.8% or less ○: 0.9~1.2% △: 1.3~1.5% ×: 1.6% or more
[0255] (20) Surface irregularities of the pattern of the coated substrate The surface unevenness of the pattern of the coated substrate was evaluated as surface roughness by scanning with an atomic force microscope (Dimension Icon, manufactured by Bruker Japan Co., Ltd.) under the conditions of contact mode, scan speed of 0.50 Hz, and scan size of 20 μm × 20 μm. The surface roughness was evaluated by classifying it as follows. Evaluation criteria; ◎: Less than 3 nm ○: 3nm or more and less than 4nm △: 4nm or more and less than 5nm ×: 5nm or more
[0256] (21) Linearity and residue of patterns on coated substrates The linearity of the pattern edges and residues on the substrate originating from silica particles were evaluated using photographic projection images (SEM images) taken with an optical microscope and a field emission scanning electron microscope (S-5500, manufactured by Hitachi High-Technologies Corporation). These were categorized and evaluated as follows: Pattern linearity assessment criteria; ◎: No jagged edges are observed on the pattern edges ○: Jagged edges are partially observed on the pattern edges. ×: Jagged edges are observed throughout the pattern edge Residue evaluation criteria; ◎: No residue found on the substrate ○: Residue is partially observed on the substrate. ×: Residue is observed over the entire surface of the substrate.
[0257] (22) Solvent resistance of patterns on coated substrates The surface unevenness of the pattern of the coated substrate after the solvent resistance test was evaluated as surface roughness by scanning with an atomic force microscope (Dimension Icon, manufactured by Bruker Japan Co., Ltd.) under the conditions of contact mode, scan speed of 0.50 Hz, and scan size of 20 μm × 20 μm. The surface roughness was evaluated by classifying it as follows. Evaluation criteria; ◎: Less than 3 nm ○: 3nm or more and less than 4nm △: 4nm or more and less than 5nm ×: 5nm or more
[0258] The linearity of the pattern edge and residues derived from silica particles on the substrate were evaluated by immersing the pattern film in PGME for 1 minute and drying at 80°C for 1 minute, and then photographing and evaluating the resulting SEM images using an optical microscope and a field emission scanning electron microscope (S-5500, Hitachi High-Technologies Corporation). These were classified and evaluated as follows: Pattern linearity assessment criteria; ◎: No jagged edges are observed on the pattern edges ○: Jagged edges are partially observed on the pattern edges. ×: Jagged edges are observed throughout the pattern edge Residue evaluation criteria; ◎: No residue found on the substrate ○: Residue is partially observed on the substrate. ×: Residue is observed over the entire surface of the substrate.
[0259] [Example 2] In the first step, Al 2 O 3 A PGME dispersion of particles was prepared, and a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that 20.0 kg of a sodium aluminate aqueous solution having a concentration of 3.5 mass% as a starting material and a pH of 12.8 was prepared, 1.5 kg of the sodium silicate aqueous solution and 0.5 kg of the sodium aluminate aqueous solution were used in the second step, 39.0 kg of the sodium silicate aqueous solution and 13.0 kg of the sodium aluminate aqueous solution were used in the third step, and the heating rate and heating temperature in the fifth step were set to 0.5°C / min and 60°C, respectively.
[0260] [Example 3] In the first step, an aqueous dispersion of silica-based particles (USBB-120 manufactured by JGC Catalysts and Chemicals Co., Ltd., average particle size 25 nm, solid content concentration 20 mass%, Al in the solid content) was 2 O 3 A PGME dispersion of particles was prepared in the same manner as in Example 1, except that 100 g of PGME (content 27% by mass) was added with 9,900 g of pure water, and then a 1% by mass aqueous sodium hydroxide solution was added to prepare 10.0 kg of an aqueous solution with a pH of 12.5. In the second step, 36.0 kg of the aqueous sodium silicate solution and 12.0 kg of the aqueous sodium aluminate solution were used, in the third step, 210.0 kg of the aqueous sodium silicate solution and 70.0 kg of the aqueous sodium aluminate solution were used, the heating rate in the fifth step was 5.0°C / min, the solution was heated to 200°C and maintained for 10 hours, and then cooled to 48°C.
[0261] [Example 4] In the first step, Al 2 O 3A PGME dispersion of particles was prepared, and a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that 20.0 kg of a sodium aluminate aqueous solution having a concentration of 4.5 mass% as a solution and a pH of 12.9 was prepared, 2.85 kg of the sodium silicate aqueous solution and 0.95 kg of the sodium aluminate aqueous solution were used in the second step, 63.0 kg of the sodium silicate aqueous solution and 21.0 kg of the sodium aluminate aqueous solution were used in the third step, and the heating temperature in the fifth step was 80°C.
[0262] [Example 5] In the first step, 9950.6 g of pure water was added to 49.4 g of an aqueous dispersion of silica particles (Cataloid SI-40 manufactured by JGC Catalysts and Chemicals Co., Ltd., average particle size 17 nm, solid content concentration 40.5% by mass), and then a 1% by mass NaOH aqueous solution was added to prepare 10.0 kg of an aqueous solution with a pH of 12.5. In the second step, the amount of sodium silicate aqueous solution was 24.6 kg, the amount of sodium aluminate aqueous solution was 8.2 kg, in the third step, the amount of sodium silicate aqueous solution was 156.0 kg, the amount of sodium aluminate aqueous solution was 52.0 kg, and in the fifth step, the heating rate was 3.0 ° C. / min, and the heating temperature was 180 ° C. In the same manner as in Example 1, a PGME dispersion of particles was produced, and a coating liquid and a coated substrate were produced.
[0263] [Example 6] A PGME dispersion of particles was prepared, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that in the second step, the amount of the sodium silicate aqueous solution was 57.0 kg, and the amount of the sodium aluminate aqueous solution was 19.0 kg, and in the third step, the amount of the sodium silicate aqueous solution was 390.0 kg, and the amount of the sodium aluminate aqueous solution was 130.0 kg.
[0264] [Example 7] In the first step, an aqueous dispersion of silica-based particles (USBB-120 manufactured by JGC Catalysts and Chemicals Co., Ltd., average particle size 25 nm, solid content concentration 20 mass%, Al in the solid content) was 2 O 3A PGME dispersion of particles was prepared, and a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that in the second step, 19.2 kg of the sodium silicate aqueous solution and 6.4 kg of the sodium aluminate aqueous solution were used, and in the third step, 90.0 kg of the sodium silicate aqueous solution and 30.0 kg of the sodium aluminate aqueous solution were used.
[0265] [Example 8] A PGME dispersion of particles was prepared in the same manner as in Example 1, except that the heating temperature in the fifth step was set to 180°C, 4.0 g of γ-methacryloxypropyltrimethoxysilane was used as an organosilicon compound in the surface treatment of the particles, and stirring was performed at 50°C for 24 hours. A coating solution and a coated substrate were produced in the same manner as in Example 1.
[0266] [Example 9] A PGME dispersion of particles was prepared, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that in the fifth step, the heating rate was set to 0.8°C / min, the heating temperature was set to 70°C, and 0.12 g of γ-methacryloxypropyltrimethoxysilane was used as the organosilicon compound in the surface treatment of the particles.
[0267] [Example 10] In the second step, SiO 2 35.4 kg of sodium silicate solution with a concentration of 3.5 mass% as a weight percent was added to the 2 O 3 A PGME dispersion of particles was produced, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that the amount of sodium aluminate aqueous solution having a concentration of 3.5 mass% as the starting material was 11.8 kg, the amount of sodium silicate aqueous solution in the third step was 273.0 kg, and the amount of sodium aluminate aqueous solution was 91.0 kg.
[0268] [Example 11] In the second step, SiO 2 29.7 kg of sodium silicate solution with a concentration of 3.5 mass% as a weight percent and Al 2 O3 A PGME dispersion of particles was produced, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that the amount of sodium aluminate aqueous solution having a concentration of 3.5 mass% as the starting material was 9.9 kg, and the amount of sodium silicate aqueous solution in the third step was 228.0 kg, and the amount of sodium aluminate aqueous solution was 76.0 kg.
[0269] [Example 12] In the second step, SiO 2 18.3 kg of sodium silicate solution with a concentration of 3.1 mass % as a weight percent was added to the 2 O 3 A PGME dispersion of particles was produced, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that 6.1 kg of a sodium aluminate aqueous solution having a concentration of 3.1 mass% as the starting material was used, and 142.5 kg of the sodium silicate aqueous solution and 47.5 kg of the sodium aluminate aqueous solution in the third step were used.
[0270] [Example 13] In the first step, Al 2 O 3 20.0 kg of a sodium aluminate aqueous solution having a concentration of 3.5 mass% as a SiO 2 solution and a pH of 12.8 was prepared. 2 4.2 kg of sodium silicate solution with a concentration of 8.0 mass% as a weight percent, 2 O 3 A PGME dispersion of particles was prepared, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that in the third step, 258.0 kg of the sodium silicate aqueous solution and 86.0 kg of the sodium aluminate aqueous solution were used, and in the fifth step, the heating rate was 0.5°C / min and the heating temperature was 60°C.
[0271] [Example 14] In the first step, Al 2 O 3 20.0 kg of a sodium aluminate aqueous solution having a concentration of 3.5 mass% as a SiO 2 solution and a pH of 12.8 was prepared. 210.8 kg of sodium silicate solution with a concentration of 5.0 mass% as a weight percent was added to the 2 O 3 A PGME dispersion of particles was prepared, and a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that in the third step, 228.0 kg of the sodium silicate aqueous solution and 76.0 kg of the sodium aluminate aqueous solution were used, and in the fifth step, the heating rate was 0.5°C / min and the heating temperature was 60°C.
[0272] [Example 15] In the second step, SiO 2 22.2 kg of sodium silicate solution with a concentration of 3.5 mass% as a weight percent and Al 2 O 3 The aqueous solution of sodium aluminate having a concentration of 3.5% by mass was 7.4 kg, and the SiO 2 54.0 kg of sodium silicate solution with a concentration of 4.5 mass% as a weight percent was added to the 2 O 3 A PGME dispersion of particles was prepared, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that 6.0 kg of an aqueous sodium aluminate solution having a concentration of 4.5 mass % as the dispersion was used.
[0273] [Example 16] A PGME dispersion of particles was prepared, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that the amount of the sodium silicate aqueous solution in the third step was 189.0 kg and the amount of the sodium aluminate aqueous solution was 63.0 kg.
[0274] [Example 17] A PGME dispersion of particles was prepared, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that tetraethoxysilane (Tama Chemical Industry Co., Ltd., orthosilicate ES28) was used as the organosilicon compound in the surface treatment of the particles.
[0275] [Example 18] A PGME dispersion of particles was prepared, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that γ-acryloxypropyltrimethoxysilane (KBM-5103 manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the organosilicon compound in the surface treatment of the particles.
[0276] [Example 19] In the first step, Al is added to pure water. 2 O 3 A sodium aluminate aqueous solution having a concentration of 22 mass% as a solution was added to obtain Al 2 O 3 9902.4 g of a sodium aluminate aqueous solution having a concentration of 2.0 mass% as a solid was prepared, and 97.6 g of an aqueous dispersion of silica particles (Cataloid SI-550 manufactured by JGC Catalysts and Chemicals, Ltd., average particle size 5 nm, solid content concentration 20.5 mass%) was added to prepare 10.0 kg of an aqueous solution having a pH of 12.7. A PGME dispersion of particles was produced in the same manner as in Example 1, except that in the second step, the amount of the sodium silicate aqueous solution was 30.0 kg, the amount of the sodium aluminate aqueous solution was 10.0 kg, and in the third step, the amount of the sodium silicate aqueous solution was 312.0 kg, and the amount of the sodium aluminate aqueous solution was 104.0 kg. A coating solution and a coated substrate were produced.
[0277] [Example 20] In the first step, an aqueous dispersion of silica-based particles (USBB-120 manufactured by JGC Catalysts and Chemicals Co., Ltd., average particle size 25 nm, solid content concentration 20 mass%, Al in the solid content) was 2 O 3 9750 g of pure water was added to 250 g of SiO2 (content 27 mass%), and then a 1 mass% aqueous solution of sodium hydroxide was added to prepare 10.0 kg of an aqueous solution having a pH of 12.5. 2 16.5 kg of sodium silicate solution with a concentration of 9.0 mass% as a weight percent was added to the 2 O 3 A PGME dispersion of particles was produced, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that the amount of sodium aluminate aqueous solution having a concentration of 9.0 mass% as the starting material was 5.5 kg, and the amount of sodium silicate aqueous solution in the third step was 168.0 kg, and the amount of sodium aluminate aqueous solution was 56.0 kg.
[0278] [Comparative Example 1] In the first step, Al is added to pure water. 2 O 3 A sodium aluminate aqueous solution having a concentration of 22 mass% as a solution was added to obtain Al 2 O 3 A PGME dispersion of particles was produced, and a coating liquid and a coated substrate were produced in the same manner as in Example 1, except that 25.0 kg of a sodium aluminate aqueous solution having a concentration of 2.5 mass% as a starting material and a pH of 12.8 was prepared, 0.30 kg of the sodium silicate aqueous solution and 0.10 kg of the sodium aluminate aqueous solution were used in the second step, 375.0 kg of the sodium silicate aqueous solution and 125.0 kg of the sodium aluminate aqueous solution were used in the third step, and the heating temperature in the fifth step was 80°C.
[0279] [Comparative Example 2] In the first step, 9925.9 g of pure water was added to 74.1 g of an aqueous dispersion of silica particles (Cataloid SI-45P manufactured by JGC Catalysts and Chemicals, average particle size 60 nm, solid content concentration 40.5% by mass), and then a 1% by mass aqueous sodium hydroxide solution was added to prepare 10.0 kg of an aqueous solution with a pH of 12.5. In the second step, the amount of the aqueous sodium silicate solution was 14.1 kg, and the amount of the aqueous sodium aluminate solution was 4.7 kg, and in the third step, the amount of the aqueous sodium silicate solution was 67.5 kg, and the amount of the aqueous sodium aluminate solution was 22.5 kg. Except for this, a PGME dispersion of particles was produced in the same manner as in Example 1, and a coating solution and a coated substrate were produced.
[0280] [Comparative Example 3] In the first step, Al is added to pure water. 2 O 3 A sodium aluminate aqueous solution having a concentration of 22 mass% as a solution was added to obtain Al 2 O 3A PGME dispersion of particles was produced, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that 10.0 kg of a sodium aluminate aqueous solution having a concentration of 2.5 mass% as a starting material and a pH of 12.8 was prepared, 4.2 kg of the sodium silicate aqueous solution and 1.4 kg of the sodium aluminate aqueous solution were used in the first step, and 360.0 kg of the sodium silicate aqueous solution and 120.0 kg of the sodium aluminate aqueous solution were used in the third step.
[0281] [Comparative Example 4] A PGME dispersion of particles was prepared in the same manner as in Example 1, except that the heating temperature in the fifth step was set to 220°C, 8.0 g of γ-methacryloxypropyltrimethoxysilane was used as an organosilicon compound in the surface treatment of the particles, and stirring was performed at 50°C for 24 hours. A coating solution and a coated substrate were produced in the same manner as in Example 1.
[0282] [Comparative Example 5] A PGME dispersion of particles was prepared, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that the heating temperature in the fifth step was 50°C and the surface treatment of the particles with an organosilicon compound was not performed.
[0283] [Comparative Example 6] In the second step, SiO 2 39.0 kg of sodium silicate solution with a concentration of 2.0 mass% as a weight percent was added to the 2 O 3 A PGME dispersion of particles was produced, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that the amount of sodium aluminate aqueous solution having a concentration of 2.0 mass% as the starting material was 13.0 kg, the amount of sodium silicate aqueous solution in the third step was 216.0 kg, and the amount of sodium aluminate aqueous solution was 72.0 kg.
[0284] [Comparative Example 7] In the first step, 9753.1 g of pure water was added to 246.9 g of an aqueous dispersion of silica particles (Cataloid SI-40 manufactured by JGC Catalysts and Chemicals, average particle size 17 nm, solid content concentration 40.5% by mass), and then a 1% by mass NaOH aqueous solution was added to prepare 10.0 kg of an aqueous solution with a pH of 12.5.2 12.0 kg of sodium silicate solution with a concentration of 1.5 mass % as a weight percent was added to the 2 O 3 A PGME dispersion of particles was produced in the same manner as in Example 1, except that the amount of sodium aluminate aqueous solution having a concentration of 1.5 mass% as the starting material was 4.0 kg, the amount of sodium silicate aqueous solution in the third step was 156.0 kg, and the amount of sodium aluminate aqueous solution was 52.0 kg. A coating solution and a coated substrate were produced.
[0285] [Comparative Example 8] In the first step, Al is added to pure water. 2 O 3 A sodium aluminate aqueous solution having a concentration of 22 mass% as a solution was added to obtain Al 2 O 3 25.0 kg of a sodium aluminate aqueous solution having a concentration of 3.0 mass% as a solution and a pH of 12.8 was prepared. In the second step, SiO 2 0.69 kg of sodium silicate solution with a concentration of 10.5 mass% as a weight percent, 2 O 3 A PGME dispersion of particles was prepared, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that the amount of sodium aluminate aqueous solution having a concentration of 10.5 mass% as the starting material was 0.23 kg, and the amount of sodium silicate aqueous solution in the third step was 375.0 kg and the amount of sodium aluminate aqueous solution was 125.0 kg.
[0286] [Comparative Example 9] In the second step, SiO 2 66.0 kg of sodium silicate solution with a concentration of 3.5 mass% as a weight percent was added to the 2 O 3 In the third step, 22.0 kg of an aqueous solution of sodium aluminate having a concentration of 3.5% by mass as a solution of SiO 2 106.7 kg of sodium silicate solution with a concentration of 4.5 mass% as a weight percent was added to the 2 O 3 A PGME dispersion of particles was prepared, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that 11.9 kg of an aqueous sodium aluminate solution having a concentration of 4.5 mass % as the dispersion was used.
[0287] [Comparative Example 10] In the second step, the amount of the sodium silicate aqueous solution was 7.2 kg, and the amount of the sodium aluminate aqueous solution was 2.4 kg, and in the third step, the amount of the sodium silicate aqueous solution was 270.0 kg, and the amount of the sodium aluminate aqueous solution was 90.0 kg. In addition, in the fourth step, the pH of the dispersion after the dropwise addition of concentrated hydrochloric acid was adjusted to pH 3.0, and while adding 4 L of a pH 3.0 hydrochloric acid aqueous solution and 2 L of pure water, the dissolved aluminum salt was separated and washed using an ultrafiltration membrane, in the same manner as in Example 1, to produce a PGME dispersion of particles, and produce a coating solution and a coated substrate.
[0288] [Comparative Example 11] A PGME dispersion of particles was prepared, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that the amount of sodium silicate aqueous solution in the third step was 150.0 kg, the amount of sodium aluminate aqueous solution was 50.0 kg, and the heating temperature in the fifth step was 250°C.
[0289] [Comparative Example 12] In the first step, Al is added to pure water. 2 O 3 A sodium aluminate aqueous solution having a concentration of 22 mass% as a solution was added to obtain Al 2 O 3 10.0 kg of a sodium aluminate aqueous solution having a concentration of 10.5% by mass and a pH of 12.9 was prepared. In the second step, SiO 2 2.4 kg of sodium silicate solution with a concentration of 10.5 mass % as a weight percent, 2 O 3 The same procedure as in Example 1 was followed, except that 0.8 kg of a sodium aluminate aqueous solution having a concentration of 10.5 mass % as the aqueous solution was used. However, since the composite oxide particles a obtained in the second step were agglomerated particles having an average particle diameter of 3 μm or more, the subsequent steps were not carried out, and neither a coating liquid nor a coated substrate was produced.
[0290] [Comparative Example 13] A PGME dispersion of particles was prepared, and a coating solution and a coated substrate were produced in the same manner as in Example 1, except that the amount of the sodium silicate aqueous solution in the third step was 69.0 kg and the amount of the sodium aluminate aqueous solution was 23.0 kg.
[0291] [Table 4]
[0292] [Table 5]
[0293] [Table 6]
[0294] [Table 7]
[0295] [Table 8]
[0296] [Table 9]
[0297] [Table 10]
Claims
1. A particle having an outer shell containing silicon and a cavity therein, The particles have an average particle size of 15 to 150 nm, a refractive index of 1.08 to 1.35, and a number density of silanol groups on the particle surface calculated by the Sears measurement method of 0.5 to 2.5 / nm 2 wherein the proportion of particles having an aspect ratio of 1.50 to 5.00 among the particles is 50% or more.
2. 2. The particle dispersion according to claim 1, wherein the particles have an average aspect ratio of 1.25 to 5.
00.
3. 2. The particle dispersion according to claim 1, wherein the cavities have an average aspect ratio of 1.00 to 6.
50.
4. 3. The particle dispersion according to claim 1, wherein the ratio (Dn / Df) of a weighted average value (Dn) of the minor axis of non-linked particles and the diameter of the constricted portion of linked particles to an average primary particle diameter (Df) is 0.20 to 0.
95.
5. 3. The particle dispersion according to claim 1, wherein the ratio (A1 / A2) of the specific surface area (A1) of the particles determined by pulse NMR measurement of the aqueous dispersion of the particles to the specific surface area (A2) of the particles determined from the average particle diameter of the particles is 0.60 or more.
6. The difference between the density of the particles in helium gas and the density in nitrogen gas is 0.2 to 1.4 g / cm 3 3. The particle dispersion according to claim 1, wherein
7. The particles 29 In Si-NMR analysis, the chemical shift of silicon atom appears at -78 to -120 ppm. 1 ~Q 4 Q that appears at a chemical shift of -108 to -120 ppm relative to the sum of the areas of the peaks representing the structure 4 3. The particle dispersion according to claim 1, wherein the area ratio of the peak representing the structure is less than 90%.
8. the particles have at least one functional group selected from an alkyl group, an acryloyl group, a (meth)acryloyl group, a vinyl group, a mercapto group, and an epoxy group; at least one functional group selected from a hydroxyl group, a carboxyl group, and an amino group; 3. The dispersion of particles according to claim 1 or 2, comprising:
9. A first step of preparing an alkaline aqueous solution; A solution of a compound containing silicon and an aqueous solution of an alkali-soluble compound of an inorganic element other than silicon are mixed together, and the oxide of silicon is converted to SiO 2 When the oxide of the inorganic element is represented as MOx, the concentration of the solution and the aqueous solution is SiO 2 and a second step of simultaneously adding the above-mentioned components to the alkaline aqueous solution so as to have a period during which the MOx content is 3.1 to 10.0 mass % and the solid content concentration of the dispersion is 2.5 mass % or more, thereby preparing a dispersion of composite oxide particles a. Next, a molar ratio (MOx / SiO 2 a third step of adding a solution of a compound containing silicon and an aqueous solution of an alkali-soluble compound of an inorganic element other than silicon to prepare a dispersion of composite oxide particles b having an average primary particle size of 15 to 150 nm, and a value obtained by subtracting the average primary particle size of the composite oxide particles a from the average primary particle size and dividing the result by 2 is 3 to 14 nm; Next, a fourth step of adding an acid to the dispersion liquid of the composite oxide particles b to remove at least a part of the elements other than silicon constituting the composite oxide particles b, thereby preparing a dispersion liquid of silica-based particles; Next, a fifth step of heating the dispersion liquid of the silica-based particles to 60 to 200° C. and then lowering the temperature to less than 50° C.; A method for producing a dispersion of particles comprising:
10. The method for producing a particle dispersion liquid according to claim 9 , wherein the alkaline aqueous solution in the first step contains an element that becomes an amphoteric oxide.
11. 10. The method for producing a particle dispersion liquid according to claim 9, further comprising the step of adding at least one of an organosilicon compound represented by the following formula (8) and a partial hydrolyzate thereof to the dispersion liquid after the fifth step: R n -SiX 4-n (8) (In the formula, R is an unsubstituted or substituted hydrocarbon group having 1 to 10 carbon atoms, X is an alkoxy group having 1 to 4 carbon atoms, a hydroxyl group, or a hydrogen atom, and n is an integer of 0 to 4.)
Citation Information
Patent Citations
Organic-inorganic hybrid photosensitive resin composition and liquid crystal display element using cured product thereof
JP2009020520A
Composition for forming cured film, and cured film formation method
JP2019119848A
Photosensitive resin composition for black resist, light-shielding film obtained by curing the same, and color filter
JP2020166156A
Chain-shaped silica-based hollow fine particles and process for producing same, coating fluid for transparent coating film formation containing the fine particles, and substrate with transparent coating film
WO2010071010A1